METHOD FOR MANUFACTURING BATTERY CELL ASSEMBLY, BATTERY CELL ASSEMBLY AND BATTERY CELL
Patent Information
- Application Number
- JP2023103946
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-12-22
- Filing Date
- 2023-06-26
- Publication Date
- 2025-02-27
- Estimated Expiration
- 2038-12-18
Smart Images

Figure 0007637189000001 
Figure 0007637189000002 
Figure 0007637189000003
Abstract
Description
[Technical field]
[0001] Claiming priority under 35 U.S.C. § 119 This patent application claims the benefit of U.S. Provisional Patent Application No. 62 / 609,796, entitled "Reliable Energy Storage Devices with Flexible Ceramic Layer Separating Electrodes," filed December 22, 2017, which is expressly incorporated by reference in its entirety.
[0002] Embodiments of the present disclosure relate generally to the design and fabrication of separators with separator layers comprising ceramics and their use in electrochemical energy storage devices and other applications, and to the design and fabrication of improved energy storage devices including separators with separator layers comprising ceramics. [Background technology]
[0003] Advanced rechargeable batteries and electrochemical capacitors are suitable for a wide range of consumer electronics, electric vehicles, grid storage, and other important applications, in part due to their relatively high energy density, relatively high specific energy, light weight, and potential long life. However, despite the increasing commercial adoption of these electrochemical energy storage devices, further development is needed, particularly for potential applications in low or zero emission hybrid or fully electric vehicles, consumer electronics, energy efficient cargo ships and locomotives, aerospace applications, and power grids. In particular, further improvements in safety, energy density, specific energy, power density, specific power, cycle stability, and calendar life are required for various electrochemical capacitors and rechargeable batteries, such as rechargeable metal and metal ion batteries (such as rechargeable Li and Li ion batteries, rechargeable Na and Na ion batteries, rechargeable Mg and Mg ion batteries, rechargeable K and K ion batteries, etc.), rechargeable alkaline batteries, rechargeable metal hydride batteries, rechargeable lead batteries, other rechargeable aqueous batteries, double layer capacitors, hybrid supercapacitors, and other devices. Additionally, improvements in energy density, specific energy, power density, specific power, and calendar life are required for various primary batteries as well as primary and rechargeable batteries operating at low temperatures (e.g., below -20°C) or high temperatures (e.g., above 60°C) (e.g., batteries used in drilling or specialized applications, such as thermal batteries, etc.).
[0004] The separator membranes of many of these primary and rechargeable electrochemical energy storage devices, such as lithium-ion (Li-ion) batteries, various aqueous batteries, and electrochemical capacitors, are generally fabricated from porous polymeric materials. These membranes must electrically insulate the anode and cathode in the cell to prevent self-discharge while at the same time allowing transport of electrolyte ions between these electrodes. Known examples of polymeric materials used in the fabrication of such membranes include olefins (such as polypropylene or polyethylene), cellulose, aramid, nylon, polytetrafluoroethylene, and the like. The selection of a polymer for a given membrane application may depend on the electrochemical and chemical stability in contact with both electrodes (anode and cathode) and the electrolyte during fabrication and operation of the device, wettability by the selected electrolyte, affordability, porosity and pore tortuosity, mechanical properties, thermal properties, and other factors. Typical thicknesses of such separator membranes in energy storage devices range from as little as 6 microns to as much as 50 microns. Substantially thinner polymer membranes become less safe to use, while substantially thicker membranes typically reduce the energy density and specific energy and power density and specific power of the energy storage device to undesirable levels. Typical porosity of such polymer membranes ranges from about 30% to about 50%, with the most typical value being about 40% for separator membranes used in certain conventional Li-ion batteries. Although polymer-based separator membranes can be mass-produced, are thin and flexible, they suffer from multiple limitations, such as limited thermal stability, limited strength and toughness (especially when fabricated thin enough), poor resistance to dendrite penetration, poor wettability by some electrolytes, and limited electrolyte permeability, among others. Such limitations become particularly problematic when energy storage devices reach their limits, e.g., when such devices require, among others, faster charging, better stability under high temperatures and stresses, longer cycling stability, and longer calendar life.
[0005] Thus, there remains a need for improved separator membranes and improved electrochemical energy storage devices in which the electrodes are electrically separated and ionically bonded. Additionally, there remains a need for improved materials and improved manufacturing processes. Summary of the Invention
[0006] SUMMARY OF THE DISCLOSURE The embodiments disclosed herein address the above needs by providing improved batteries, components, and other related materials and manufacturing processes.
[0007] In one example, the separator is disposed with a separator layer comprising a ceramic, the separator layer having a diameter in the range of about 3 nm to about 2 microns, an aspect ratio in the range of about 20 to about 100,000, and a surface area of about 0.01 cm 3 / g ~ approx. 1cm 3 The porous metal oxide fibers include porous metal oxide fibers having a total open pore volume between the porous metal oxide fibers in the range of 100 / g. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 illustrates an example battery (e.g., Li-ion or Na-ion, etc.) to which the components, materials, methods, and other techniques described herein, or combinations thereof, may be applied in accordance with various embodiments. [Diagram 2] FIG. 1 shows an example of a ceramic separator made from Al2O3 nanofibers. [Diagram 3] 1A-1D are cross-sectional scanning electron microscope (SEM) images showing various aspects of ceramic separators made from small Al2O3 fibers. [Figure 4] FIG. 1 shows an example of a separator layer coating of small Al2O3 fibers deposited directly onto a portion of a Si-based Li-ion battery anode on a copper foil current collector. The separator coating was deposited from a dispersion of small Al2O3 fibers. [Diagram 5]Figure 1 shows the performance of four full cells with Si-based Li-ion battery anodes constructed with either a small Al2O3 fibrous separator layer (thickS SAnode and thinS SAnode) (of two thicknesses) directly coated onto a high-voltage LCO cathode and Si anode, and similar (control) cells (Control 4 and Control 5) fabricated using a regular commercial polymer (PP) separator. All cells are constructed with identical anodes and cathodes. Capacity (mAh / g) is normalized by the weight of the anode coating. Mid-cycle hysteresis (V) is recorded when the cells are cycled at C / 2 rate. [Figure 6] FIG. 1 illustrates a separator membrane including small oxide fibers made according to an embodiment of the present disclosure. [Figure 7A] FIG. 1 illustrates a separator membrane including small oxide fibers made according to an embodiment of the present disclosure. [Figure 7B] FIG. 1 illustrates a separator membrane including small oxide fibers made according to an embodiment of the present disclosure. [Figure 8A] FIG. 1 shows several example schematics of membranes containing several types of small fibers made according to embodiments of the present disclosure. [Figure 8B] 1 illustrates several example schematics of membranes containing several types of small fibers made according to embodiments of the present disclosure. [Figure 8C] FIG. 1 shows several example schematics of membranes containing several types of small fibers made according to embodiments of the present disclosure. [Figure 8D] FIG. 1 shows several example schematics of membranes containing several types of small fibers made according to embodiments of the present disclosure. [Figure 8E] FIG. 1 shows several example schematics of membranes containing several types of small fibers made according to embodiments of the present disclosure. [Figure 8F] FIG. 1 shows several example schematics of membranes containing several types of small fibers made according to embodiments of the present disclosure. [Figure 8G]FIG. 1 shows several example schematics of membranes containing several types of small fibers made according to embodiments of the present disclosure. [Figure 8H] FIG. 1 shows several example schematics of membranes containing several types of small fibers made according to embodiments of the present disclosure. [Figure 8I] FIG. 1 shows several example schematics of membranes containing several types of small fibers made according to embodiments of the present disclosure. [Figure 8J] FIG. 1 shows several example schematics of membranes containing several types of small fibers made according to embodiments of the present disclosure. [Figure 9] FIG. 2 illustrates an example of a ceramic platelet that may be used in a separator layer coating according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The accompanying drawings are presented to aid in the description of embodiments of the present disclosure and are provided solely for purposes of illustrating the embodiments, not limiting them. Unless otherwise stated or implied by context, different hatching, shading, and / or fill patterns in the drawings are intended only to depict contrasts between different components, elements, features, etc., and are not intended to convey the use of specific materials, colors, or other characteristics that may be defined outside of this disclosure for the particular patterns employed.
[0010] Aspects of the invention are disclosed in the following description and associated drawings directed to specific embodiments of the invention. The term "embodiments of the invention" does not require that all embodiments of the invention include the discussed features, advantages, processes, or modes of operation, and alternative embodiments may be devised without departing from the scope of the invention. Furthermore, well-known elements of the invention may not be described in detail or may be omitted so as not to obscure other more relevant details. Furthermore, the term "at least partially" is intended to be interpreted as "partially, substantially, or completely."
[0011] Any numerical range described herein with respect to any embodiment of the invention is intended not only to define upper and lower limits of the relevant numerical range, but also to implicitly disclose each discrete value within that range with units or increments consistent with the level of precision characterizing the upper or lower limit. For example, a numerical range of distances from 7 nm to 20 nm (i.e., a precision level with a unit or increment of 1) encompasses the set [7, 8, 9, 10, ..., 19, 20] (in nm) just as if the intervening numbers 8 to 19 were expressly disclosed with a unit or increment of 1. In another example, a percentage numerical range (i.e., a precision level of hundredths or increments) from 30.92% to 47.44% encompasses (in %) the set [30.92, 30.93, 30.94, ..., 47.43, 47.44], as if the intervening numbers between 30.92 and 47.44 were expressly disclosed in hundredths or increments. Thus, any numbers contained in a disclosed numerical range are intended to be construed as if those intervening numbers were expressly disclosed, and such intervening numbers may thereby constitute their own upper and / or lower limits of subranges falling within the broader range. Each subrange (e.g., each range that includes at least one intervening number from the broader range as an upper and / or lower limit) is thereby intended to be construed as implicitly disclosed by the explicit disclosure of the broader range.
[0012] The description of one or more embodiments below may describe specific examples in the context of aluminum- (Al-) or oxygen- (O-) containing small (nano)wires, whiskers, (nano)fibers, (nano)ribbons, other elongated particles, and particles of other planar shapes, including flakes (alternatively sometimes referred to as "platelets"), (nano)sheets, various porous elongated particles, or porous planar particles, although it will be understood that various aspects may be applicable to other compositions, such as elongated particles of various ceramics, including other metal oxides, metal oxyfluorides, metal fluorides, metal oxynitrides, metal oxyhydroxides (e.g., clays and other oxyhydroxides), metal nitrides, metal oxynitrides, metal carbides, metal oxycarbides, and metal compositions. Examples of metal (or metalloid) atoms suitable for such compositions can include (but are not limited to) at least one of the following or combinations thereof (depending on the particular application): Al, Si, Ti, Li, Cu, Fe, Mg, Na, K, Cs, Ba, Be, C, Zn, Cr, Zr, Y, La, Ce, Sm, Mo, Nb, Ta, W, Ag, Ag, Pt, to name a few.
[0013] The description of one or more embodiments below may describe specific examples in the context of small (nano)wires, whiskers, (nano)fibers, (nano)ribbons, other elongated particles, as well as flakes, (nano)sheets, various porous elongated particles or porous planar particles comprising a single metal (e.g., aluminum) in the composition, and other planar shaped particles, although it will be understood that various aspects may be applicable to compositions comprising two, three or more metals.
[0014] The description of one or more embodiments below may describe specific examples in the context of particular types of particles (e.g., (nano)fibers or flakes), but it will be understood that various aspects may be applicable to compositions comprising particles of different shapes (e.g., combinations of fibrous and flake-like particles) and may exhibit different compositions, microstructures or sizes.
[0015] Although the description of one or more embodiments below may describe specific examples in the context of pure metal oxides, it will be understood that various aspects may be applicable to compositions that may include both oxides and portions of neighboring species of oxides, such as hydroxides (hydrogen atoms bonded to oxygen atoms), suboxides (oxygen atoms bonded to oxygen atoms), carboxylates (metal atoms bonded to carbonate groups), hydrides (metal atoms bonded to hydrogen), nitrides (metal atoms bonded to nitrogen), fluorides (metal atoms bonded to fluorine), among many others. Thus, the coordination number of metal atoms in such compositions may differ from the coordination number of the pure oxide.
[0016] Although the description of one or more embodiments below may describe specific examples in the context of a pure alkoxide, it will be understood that various aspects may be applicable to compositions that may include both alkoxides and moieties of adjacent species of the alkoxide, such as hydroxides (containing hydrogen bonded to an oxo group), suboxides (containing oxygen bonded to an oxo group), carboxylates (oxygen bonded to a carbonate group), nitrides (oxygen bonded to a nitrogen), among others. Thus, the coordination number of the metal atom in such a composition may differ from that of the pure alkoxide, and the ratio of alcohol groups (-ROH) to metal atoms may differ from that of the pure alkoxide. For example, in the case of an aluminum ethoxide composition, the aluminum (Al) atom is (pure Al(EtOH) 3 The Al atoms may not be 6-coordinated (as would be expected in the formula 1), but may contain, for example, 6-coordinated, 5-coordinated, and 4-coordinated Al. Similarly, the molar ratio of ethoxy groups (-EtOH) to Al atoms is (pure Al(EtOH) 3 The expected variance may not be exactly 3, but may vary, for example, from as high as 10 to as low as 0.1.
[0017] In the context of one or more embodiments of this description, the term "bulk" (e.g., "bulk small fibers," "bulk small particles," "bulk small flakes," etc.) refers to a sample in which particles (e.g., small fibers, small flakes, and other small particles) are stuck together by chemical, electrostatic, and / or physical mechanisms to form larger agglomerates (average dimensions of such agglomerates range from about 1 pm to about 10 cm).
[0018] In the context of one or more embodiments of this description, the term "aspect ratio" refers to the ratio of the longest dimension to the shortest dimension of a material or particle.
[0019] In the context of one or more embodiments of the present description, the term "dispersion" refers to a mixture of one or more solids and one or more liquids, where the one or more solids interact with the one or more liquids in a way that changes the fluid properties of both the one or more solids and the one or more liquids. For example, dispersing solid (nano)particles of various shapes and sizes in a liquid increases the viscosity of the liquid and increases the Brownian motion of the particles. The term "dispersion" may also refer to a state when solid (nano)particles of various shapes and sizes are suspended in a liquid (solvent). The term "stable dispersion" refers to a state in which the particles (e.g., fibers, flakes, nanoparticles, or particles of various other shapes and sizes) remain suspended for a time scale sufficient for a given processing step (e.g., casting the dispersion into a film on a substrate, etc.).
[0020] The description of one or more embodiments below may also describe specific examples in the context of the formation and application of particular oxides of one or more metals, although it will be understood that various aspects of the present disclosure may be applicable to the formation of other ceramic materials (not necessarily oxides) as well as a variety of ceramic-ceramic, ceramic-glass, ceramic-metal, ceramic-carbon, ceramic-polymer, glass-polymer, glass-ceramic-polymer, polymer-polymer and other composite materials.
[0021] Although the description of one or more embodiments below may also describe specific examples in the context of the formation and application of porous membranes for electrochemical energy storage or energy conversion devices, it will be understood that various aspects of the present disclosure (such as, in particular, the formation of the membranes) may be applicable to a wide range of other applications, such as, in particular, various composite materials, biomedical and medical applications, sensors (including but not limited to humidity sensors), air and liquid membrane purification (including but not limited to, the filtration or purification of various gases or liquids from small particles (e.g., HEPA filtration, etc.), bacteria, bacterial spores, viruses, harmful organics, etc.), structural materials and devices, optical devices, electrical or thermal insulation, etc.
[0022] For simplicity and illustrative purposes, any elongated particle having a suitable size, shape, aspect ratio, density, porosity, crystal structure, and morphology (e.g., dense and porous nanofibers and fibers, nanowires, whiskers, nanotubes, nanoribbons, etc.) may be generally referred to herein as a "small fiber." In one or more embodiments of the present disclosure, suitable diameters (or widths) of individual small fibers (of various compositions) may range from about 2 nm to about 1 micron, and suitable lengths of individual small fibers (of various compositions) may range from about 50.0 nm to about 500.0 mm. In one or more embodiments of the present disclosure, suitable aspect ratios (width to length) of individual small fibers (of various compositions) may range from about 1:4 to about 1:1,000,000.
[0023] For simplicity and illustrative purposes, all planar particles of suitable size, shape, aspect ratio, density, porosity, crystal structure, and morphology are generally referred to herein as "small flakes." In one or more embodiments of the present disclosure, suitable thicknesses of individual small flakes (of various compositions) may range from about 0.3 nm to about 0.6 microns, and suitable average widths of individual small flakes may range from about 50 nm to about 5 mm. In one or more embodiments of the present disclosure, suitable aspect ratios (width to length) of individual small flakes (of various compositions) may range from about 1:4 to about 1:1,000,000.
[0024] For simplicity and illustrative purposes, a volume of approximately 0.2 microns 3 All particles smaller than this size may be generally referred to herein as "nanoparticles."
[0025] Depending on the application, in one example, suitable true densities (taking into account closed porosity) for small fibers, small flakes and nanoparticles in the context of one or more embodiments of the present description may range from about 0.3 to about 4 g / cm. 3 (e.g., for particles containing only Al metal in their composition) and about 6 g / cm 3 Depending on the application and processing conditions, in one example, suitable pore volumes (e.g., total open pore volume) between individual small fibers, small flakes, and nanoparticles (e.g., including the pore space of the fibers / flakes / nanoparticles themselves, e.g., surface pores, etc., plus the intervening open pore space between the fibers / flakes / nanoparticles when disposed in a separator layer that includes a ceramic) can range from about 0 to about 5 cm. 3 / g (e.g., in some designs, approximately 0.01 cm 3 / g ~ approx. 1cm 3 / g). Depending on the application and processing conditions, in one example, the microstructure can range from amorphous to nanocrystalline, nanocrystalline to polycrystalline, polycrystalline to single crystal, single crystal to mixtures thereof, mixtures thereof to other types. Depending on the application and processing conditions, in one example, suitable surface roughness for small fibers and small flakes can range from about 0 to about 100 nm.
[0026] Certain conventional polymer separator membranes used in Li-ion, Na-ion and other rechargeable and primary batteries, as well as electrochemical capacitors (e.g., double layer capacitors, pseudocapacitors or hybrid devices), and select types of fuel cells, have limited mechanical strength and poor thermal stability, such that failure of such polymer separator membranes can lead to thermal runaway and cell explosion. Reducing the thickness of the polymer separator membranes would be advantageous in some applications to increase the energy and power density of these energy storage devices, but reducing the thickness of the polymer separator membranes is conventionally not feasible because it would degrade the mechanical properties to a level where the operation of the cell becomes unsafe, making the likelihood of the separator failing during cell operation unacceptably high. Certain conventional polymer separator membranes may further suffer from limited wettability by the electrolyte and limited permeability by the electrolyte ions, which can limit the charge rate and power characteristics of the electrochemical energy storage device.
[0027] Ceramic materials are known to exhibit good strength, good wettability, and good thermal properties compared to polymers, but are generally too brittle to be used as separator membranes. However, when ceramic materials are processed into various fibers (especially small fibers), the fibrous ceramic materials can be flexible enough to be used as separator membranes according to one or more embodiments. Moreover, in some designs, reducing the diameter of the ceramic fibers may increase the specific strength and toughness of the fibers, as well as other mechanical properties (when normalized by the mass or cross-sectional area of the fibers). Thus, forming flexible, strong, and thermally stable ceramic separators from small ceramic fibers (and other materials) can overcome one or more limitations of conventional polymeric separators. However, economical formation of high-performance ceramic separators is difficult. One or more embodiments of the present disclosure are directed to suitable fabrication methods, suitable forms, and suitable compositions of ceramic-containing (or pure ceramic) separator layers (e.g., standalone separator films independent of electrodes, or separator coatings directly coated onto electrodes and / or separator films) for metal ion batteries based on Li-ions, Na-ions, K-ions, Ca-ions, Zn-ions, Cu-ions, Mg-ions, and other rechargeable and primary batteries (including thermal batteries) and electrochemical capacitors (including double layer capacitors).
[0028] Due to the widespread adoption and popularity of metal-ion batteries (such as Li-ion batteries), for brevity and convenience, the following description may describe specific examples in the context of Li and Li-ion batteries, but it will be readily understood that the various embodiments described below may be applied to other metal-ion battery types.
[0029] In some designs, the separator membrane (or separator membrane layer) containing ceramic fibers (including small ceramic fibers) is approximately 0.02 cm 3 / g~approx.6.00cm 3 / g (most commonly about 0.2 to about 1.5 cm3 / g) For example, a pore volume that is too small may not provide sufficient permeability, while a pore volume that is too large may reduce the mechanical strength of the membrane below desirable levels for some applications (e.g., Li-ion and other rechargeable batteries).
[0030] 1 shows an example of a metal-ion (e.g., Li-ion) battery to which the components, materials, methods, and other techniques described herein, or combinations thereof, may be applied according to various embodiments. A cylindrical battery is shown here for illustrative purposes, but other types of configurations may be used as needed, including prismatic or pouch-type (laminated) batteries, or flexible or coin-type batteries. The example battery 100 includes a negative anode 102, a positive cathode 103, a separator 104 interposed between the anode 102 and the cathode 103, an electrolyte (not shown) that impregnates the separator 104, a battery case 105, and a sealing member 106 that seals the battery case 105.
[0031] Both liquid and solid electrolytes can be used in some or all of the designs described herein. In one example, the specific electrolyte for this type of Li-based or Na-based battery is a single Li or Na salt (e.g., LiPF for Li-ion batteries). 6 , NaPF for Na-ion batteries 6 or NaClO 4The electrolyte may include an electrolyte such as a molten salt (salt) in a mixture of organic solvents (e.g., a mixture of carbonates). Other common organic solvents include nitriles, esters, sulfones, sulfoxides, phosphorus-based solvents, silicon-based solvents, ethers, etc. Such solvents may be modified (e.g., sulfonated or fluorinated). The electrolyte may also include an ionic liquid (in some designs, neutral ionic liquids; in other designs, acidic and basic ionic liquids). In some designs, a suitable electrolyte may include or be based on a molten salt (in some designs, such electrolytes may be melt-impregnated into the electrodes and / or ceramic-based separator membranes or coatings). In some designs, a suitable electrolyte may include a solid-state glass or ceramic electrolyte that exhibits a melting point below that of the ceramic membrane (or layer) and has low solubility in the membrane material at the melt-impregnation temperature (e.g., solubility of about 0-5% by volume of one or more membrane materials). In some designs, the solid-state electrolyte may be dissolved in a solvent, impregnated into a ceramic separator, and formed by firing (e.g., by using common sol-gel processing techniques).
[0032] The electrolyte can also include mixtures of different salts (eg, a mixture of several Li salts or a mixture of Li and non-Li salts for rechargeable Li and Li-ion batteries).
[0033] For example, a common salt used in the electrolyte of Li-ion batteries is LiPF 6 However, a less common salt is lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ), lithium bis(oxalato)borate (LiB(C 2 O 4 ) 2 , lithium difluoro(oxalato)borate (LiBF 2 (C 2 O 4 )), various lithium imides (e.g. SO 2 FN - (Li + )SO 2 F, C.F. 3SO 2 N - (Li + )SO 2 CF 3 、CF 3 CF 2 SO 2 N - (Li + )SO 2 CF 3 、CF 3 CF 2 SO 2 N - (Li + )SO 2 CF 2 CF 3 、CF 3 SO 2 N - (Li + )SO 2 CF 2 OCF 3 、CF 3 OCF 2 SO 2 N - (Li + )SO 2 CF 2 OCF 3 、C 6 F 5 SO 2 N - (Li + )SO 2 CF 3 、C 6 F 5 SO 2 N - (Li + )SO 2 C 6 F 5 またはCF 3 SO 2 N - (Li + )SO 2 PhCF 3Electrolytes for Na-ion, Mg-ion, K-ion, Ca-ion, Cu-ion, Zn-ion and other metal-ion batteries are often more exotic because these batteries are in earlier stages of development. For example, such exotic electrolytes may contain different salts and solvents (in some cases, ionic liquids or molten salts may replace organic solvents for certain applications).
[0034] Conventional electrodes utilized in Li-ion batteries can be fabricated by (i) forming a slurry containing active material, conductive additives, binder solution, and, optionally, surfactants or other functional additives; (ii) casting the slurry onto a metal foil (e.g., Cu foil for most anodes and Al foil for most cathodes); and (iii) drying the cast electrode to completely evaporate the solvent.
[0035] Conventional cathode materials utilized in Li-ion batteries may be of the intercalation type, where metal ions are inserted into and occupy interstitial positions in such materials during charging or discharging of the battery. Such cathodes undergo very little volume change when used in an electrode. Such conventional cathode materials also generally have high density (e.g., 3.8-6 g / cm at active material levels). 3 ) and are relatively easy to mix in a slurry. However, such cathodes exhibit relatively low gravimetric and volumetric capacities (e.g., less than about 220 mAh / g and about 800 mAh / cm, respectively). 3 less than).
[0036] Conversion-type cathode materials for rechargeable Li-ion or Li batteries may offer higher energy density, higher specific energy, or higher specific or volumetric capacity compared to intercalation-type cathode materials. For example, fluoride-based cathodes can provide greater than 300 mAh / g in some cases (1200 mAh / cm at the electrode level). 3 Due to its very high dosage (> 10 ...3 provides a theoretical specific capacity of 712 mAh / g; FeF 2 provides a theoretical specific capacity of 571 mAh / g; MnF 3 provides a theoretical specific capacity of 719 mAh / g; CuF 2 provides a theoretical specific capacity of 528 mAh / g; 2 provides a theoretical specific capacity of 554 mAh / g; PbF 2 provides a theoretical specific capacity of 219 mAh / g; 3 provides a theoretical specific capacity of 302 mAh / g; 5 provides a theoretical specific capacity of 441 mAh / g; SnF 2 provides a theoretical specific capacity of 342 mAh / g; 4 provides a theoretical specific capacity of 551 mAh / g; SbF 3 provides a theoretical specific capacity of 450 mAh / g; SbF 5 provides a theoretical specific capacity of 618 mAh / g; CdF 2 provides a theoretical specific capacity of 356 mAh / g; 2 provides a theoretical specific capacity of 519 mAh / g. Mixtures of fluorides (e.g., in the form of alloys) may provide approximately calculated theoretical capacities according to the law of mixtures. The use of mixed metal fluorides can sometimes be advantageous (e.g., may provide higher rates, lower resistance, higher practical capacity, or longer stability). In the fully lithiated state, the metal fluoride transforms into a composite material containing a mixture of metal and LiF clusters (or nanoparticles). An example of a globally reversible reaction of a conversion-type metal fluoride cathode includes the reaction of CuF 2 In the case of the cathode of the system, 2Li+CuF 2 ⇔2LiF+Cu, or FeF 3 In the case of the cathode of the system, 3Li+FeF 3 3LiF+Fe). It will be appreciated that metal fluoride-based cathodes can be prepared in both Li-free, partially lithiated, or fully lithiated states. Another example of a promising conversion-type cathode (or anode, as the case may be) is sulfur (S) (Li-free) or lithium sulfide (Li2 S, fully lithiated state). To reduce dissolution of the active material during cycling, or to improve electrical conductivity, S / Li 2 To improve the mechanical stability of the S electrode, porous S, Li 2 S, porous SC composite, Li 2 SC composites, porous S-polymer composites, or S or Li 2 Other composite formulations containing tungsten, tungsten, tungsten, fluorine, arsenic, stearate, fluorine, arsenic, fluorine ...
[0037] Unfortunately, many conversion-type cathodes used in Li-ion batteries suffer from various performance limitations in conventional cell designs. For example, such electrodes can change volume during cycling, creating stresses inside the separator that can eventually fail, especially if the separator is made of a polymer (this becomes even more problematic if the cell operates at high temperatures). Therefore, the use of a more robust ceramic separator layer (e.g., a stand-alone separator membrane or separator coating) may be particularly advantageous in cells that include conversion-type cathodes. In another example, such cathodes can begin to leach ions, which can migrate through the separator to the anode, where they can cause damage to the solid electrolyte phase-interface (SEI) layer. This can cause capacity loss and increased resistance. Polymer separators generally cannot trap such ions, thereby causing the cell to fail. The use of ceramic separators can be advantageous, since the polar nature of the ceramic separator can cause adsorption of such ions, thereby improving cell stability. In yet another example, dissolution of a portion of a conversion-type cathode may induce reprecipitation of dissolution products (such as polysulfides in the case of S-containing cathodes) at the electrode-polymer separator interface, blocking ion transport. In contrast, a ceramic separator may reduce the formation of some of the most soluble species (such as longer chain polysulfides in the case of S-containing cathodes) or adsorb them to the interior surface or decompose them into less soluble species. In this regard, the use of a ceramic separator with a high specific surface area and high porosity (e.g., in the range of about 20.0 vol.% to about 95.0 vol.%, in some designs in the range of about 30.0 vol.% to about 85.0 vol.%) may be particularly advantageous. In yet another example, a conversion-type active material may require operation of the cell at high temperatures (e.g., between about 30°C to about 300°C; e.g., to improve charge / discharge rates) where a polymer separator may fail. In contrast, a ceramic separator may operate effectively at such high temperatures.
[0038] Conventional anode materials utilized in Li-ion batteries may also be of the intercalation type, where metal ions are inserted into and occupy interstitial positions of such materials during charging or discharging of the battery. Such anodes undergo very small volume changes when used in electrodes. However, such anodes exhibit relatively small gravimetric and volumetric capacities (e.g., rechargeable specific capacities of less than 370 mAh / g and 600 mAh / cm for graphite- or carbon-based anodes). 3 (Rechargeable volumetric capacity of less than 10 ... In addition to anodes that include alloyed-type active materials, other types of high capacity anodes of interest can include conversion-type anode materials, such as metal oxides (including silicon oxide, lithium oxide, etc.), metal nitrides, metal phosphides (including lithium phosphide), metal hydrides, and the like.
[0039] Unfortunately, many alloyed or conversion type anodes used in Li-ion batteries suffer from various performance limitations in conventional cell designs. For example, such anodes can change volume during cycling, creating stresses inside the separator that can eventually fail, especially if the separator is made of a polymer (which becomes even more problematic when the cell operates at high temperatures). The use of more robust ceramic (or ceramic-containing) separator layers (e.g., standalone separator membranes or separator coatings) described herein can be particularly advantageous in cells that include alloyed or conversion type anodes. In some designs, alloyed or conversion type anodes are used in Li-ion batteries designed to achieve fast charging because their thinness (compared to graphite) allows the cell to withstand higher charging currents without failure. Unfortunately, conventional polymer membranes are substantially resistant to fast charging, inducing undesirably high voltage drops in the cell and potentially causing the anode or cathode potential to exceed safety limits. In some designs, the use of a ceramic (or ceramic-containing) separator layer (e.g., a stand-alone separator membrane or separator coating) described herein in place of a polymeric membrane may allow for faster ion transport (e.g., smaller voltage drop) and therefore may be particularly advantageous for use in such cells (especially cells designed to be charged from a discharged state (or about 0-10% of its full capacity) to about 80-90% of its full capacity in less than about 30-40 minutes, including cells containing high capacity alloyed or conversion type anode materials). In some designs, the use of a thin (e.g., about 0.5 microns to about 10 microns) ceramic separator layer (e.g., a stand-alone separator membrane or separator coating) with high (e.g., about 40-90%) internal porosity is advantageous for fast charge cells (cells designed or capable of being charged from a discharged state (or about 0% of its full capacity) to about 80% of its full capacity in less than about 30-40 minutes (or even less than 20 minutes)).
[0040] In some designs, alloyed or conversion type anodes (and / or conversion type cathodes) are used in Li-ion batteries designed to achieve the highest possible specific energy or high energy density. Unfortunately, conventional polymer membranes are generally somewhat thick (e.g., thinner polymer membranes may be unsafe), which may limit the achievable energy storage characteristics. In some designs, the use of a thin (e.g., about 0.5 microns to about 10 microns) but safe ceramic separator layer (e.g., a stand-alone separator membrane or separator coating described herein) in place of the polymer membrane may result in higher energy storage characteristics and may therefore be particularly advantageous for use in such high specific energy or high energy density cells. In some designs, the use of a separator layer (e.g., a standalone separator membrane or separator coating) may be particularly advantageous in cells with a specific energy greater than about 270 Wh / kg (e.g., more so for cells with a specific energy greater than about 350-400 Wh / kg) or an energy density greater than about 650 Wh / L (e.g., more so for cells with an energy density greater than about 750-850 Wh / L). Because higher energy density cells may release more energy internally during a self-discharge event in some designs, the use of a more thermally and mechanically stable ceramic separator layer (e.g., a standalone separator membrane or separator coating) may also be advantageous from an improved safety standpoint.
[0041] Overall, high power, fast charging, or high energy cells (including cells with conversion or alloyed anodes or conversion cathodes) can benefit in some designs when a ceramic separator membrane (or ceramic separator layer) is used in the construction.
[0042] Additionally, in some designs, one or more specialized cells that operate at high temperatures (e.g., operate at temperatures between about 70° C. and about 500° C. for at least a portion (e.g., between about 0.1% and about 100%) of their operating (charge or discharge) time) may benefit from including a thin (and potentially flexible), more thermally stable porous ceramic (or ceramic-containing) separator layer (e.g., a stand-alone separator membrane or separator coating), as described herein, especially one that includes small ceramic fibers or small ceramic flakes.
[0043] In some designs, electrically isolated ceramic separator membranes suitable for energy storage devices (e.g., Li-ion and Na-ion batteries, high temperature batteries, primary batteries, electrochemical capacitors, among others) may be fabricated from small fibers of suitable size and aspect ratio. In some designs, small ceramic flakes may be used instead of or in addition to small ceramic fibers (e.g., to provide more robust electrical isolation between electrodes or to improve the mechanical properties of the separator, since the flakes may present a larger contact area with the fibers than with other fibers in the case of randomly arranged fibers, which may allow for stronger bonding). In some designs, nanoparticles may be used in addition to small ceramic flakes and / or small ceramic fibers. Note that in some designs, when the flakes are oriented parallel to the plane of the separator layer, the presence of the flakes increases the tortuosity of the separator pores, resulting in a slower ion transport rate for a given thickness of the separator. This is one of the reasons why it is advantageous for the flake-shaped particles to not exceed about 90.0% by weight of the final layer composition (preferably 50.0% by weight or less in some designs) and not exceed about 40.0% by volume of the total volume of the separator layer (preferably less than about 20.0% by volume in some designs). In some designs, it may be advantageous to use smaller sized flakes (e.g., those having lateral dimensions in the range of about 10 nm to about 10 microns). Overall, the use of flake-shaped particles may be very advantageous in terms of the ability of the strained and stressed separator layer to prevent fracture and / or the formation of internal short circuits during cell operation, but is somewhat counterintuitive to those in the art. In some designs, it may be advantageous for the small ceramic flakes to contain pores (or channels) for improving ion transport. In some designs, such pores may be oriented approximately perpendicular to the flat areas of the flakes. In some designs, the characteristic dimension of the pores (eg, width in the case of slit-shaped pores, or diameter in the case of cylindrical pores) may range from about 0.5 nm to about 500 nm.In some designs, small pores (e.g., below a first characteristic dimension threshold) may not provide fast enough ion transport, while large pores (e.g., above a first characteristic dimension threshold or a second characteristic dimension threshold higher than the first characteristic dimension threshold) may not provide sufficient electrical isolation between the anode and cathode in the cell. In some designs, it may be advantageous for small ceramic fibers to include pores (e.g., open pores or surface pores).
[0044] In some designs, it may be advantageous to combine different sized small fibers in the membrane (e.g., having various subsets of small fibers that differ in average diameter by about 10-100 times, or that differ in length by about 10-1,000,000 times) to achieve a combination of good mechanical properties, good transport properties, and good reliable separation. In some designs, small fibers can be combined with larger fibers (e.g., fibers with diameters greater than about 1 micron, or lengths greater than about 100 microns) to achieve a good combination of membrane mechanical and transport properties. In some designs, it may be advantageous to utilize about 10% to about 100% by weight of ceramic fibers with diameters ranging from about 10 nm to about 200 nm. In some designs, it may be advantageous to utilize about 20% to about 100% by weight of ceramic fibers with diameters ranging from about 20 nm to about 200 nm. In some designs, it may be advantageous to utilize about 10% to about 100% by weight of ceramic fibers with lengths ranging from about 1 micron to about 500 microns. In some designs, it may be advantageous to utilize about 20% to about 100% by weight of ceramic fibers with lengths ranging from about 2 microns to about 200 microns. In some designs, the desired change in fiber size may also be calculated when comparing the average diameter of the thinnest 10% of the fibers to the average diameter of the thickest 2% or when comparing the average length of the shortest 10% of the fibers to the average length of the longest 2%.
[0045] In some designs, it may be advantageous to combine small flakes of different sizes in the membrane (e.g., having small flakes that differ in thickness by about 3-30 times, or that differ in lateral dimensions of the small flakes by about 3-300 times) to achieve a combination of good mechanical properties, good transport properties, and good reliable separation. In some designs, small flakes may be combined with large flakes to achieve a good combination of membrane mechanical and transport properties. In some designs, porous flakes may be combined with non-porous flakes (e.g., for similar reasons). In some designs, it may be advantageous to combine one or two or more types of flakes of different sizes (or different compositions, porosity or surface chemistry) with one or two or more types of fibers of different sizes (or different compositions, porosity or surface chemistry) in the separator layer to achieve the most favorable performance characteristics (mechanical properties and ion transport rates).
[0046] In some designs, the use of small fibers or small flakes of oxides (e.g., consisting of aluminum oxide or lithium aluminum oxide, magnesium oxide, magnesium aluminum oxide, lithium magnesium aluminum oxide, zirconium oxide, among other compositions) for the formation of a ceramic separator layer (e.g., a stand-alone separator membrane or separator coating) can be particularly advantageous for Na-ion or Li-ion batteries (as well as other types of batteries and electrochemical capacitors) that include organic, polymer, ionic liquid, or molten salt (or molten impregnated solid) electrolytes. In some designs, advantages of using oxide fibers (especially small fibers) with aspect ratios in the range of about 4-10 to about 1,000,000 in ceramic separator layers (e.g., stand-alone separator membranes or separator coatings) rather than "ordered" oxide particles with aspect ratios in the range of about 1 to about 2-4 include high fiber flexibility, high fiber strength, high fiber toughness, the ability to achieve very high porosity when randomly packing the fibers (e.g., about 70% or more, which can be important for high permeability), and the increased area of bonding or entanglement possible between fibers (compared to interactions between particles with lower aspect ratios). These may include stronger interactions (through interdigitation), enhanced robustness (or resistance to crack formation or propagation) when the electrode thickness is changed, enhanced robustness (or resistance to crack formation or propagation) when the area of the electrode is expanded somewhat (e.g., within about 0.1-20%), the ability to achieve smaller pore sizes (e.g., this may be important in preventing potential Li dendrite penetration or internal shorting upon electrical contact of the anode and cathode), as well as the ability to prepare thin porous separator layers (e.g., standalone separator membranes or separator coatings) with low surface roughness and low percentage of defects. In some designs, the advantage of using porous small ceramic fibers (e.g., from about 0.05 vol.% up to about 90 vol.%, preferably about 5 vol.% to about 40 vol.% porosity) over dense small ceramic fibers (and porous small flakes over dense small flakes) is that for the same particle packing density, the porosity is higher (and therefore more permeable).Moreover, the porous small fibers (and possibly small flakes) may be less densely packed than regular wires due to their high surface roughness and low density, which further increases the permeation of the separator layer (e.g., standalone separator membrane or separator coating). Moreover, porous ceramic fibers or flakes (even when filled with electrolyte) are lighter than dense (e.g., substantially non-porous) ceramic fibers or flakes, which is advantageous in terms of increasing the cell gravimetric energy density. Moreover, porous ceramic fibers or flakes may provide a larger surface area (e.g., if necessary to neutralize side reaction products) and may be filled with functional (nano)particles or coatings. The advantages of using smaller ceramic fibers (and smaller ceramic flakes) (e.g., fibers having diameters of about 2 nm to about 1 micron and lengths of about 50 nm to about 5 mm, or flakes having average thicknesses of about 0.3 nm to about 0.6 microns and average widths of about 50 nm to about 5 mm) over larger ceramic fibers (and larger ceramic flakes) (e.g., fibers having diameters of about 1 micron to about 20 microns or flakes having average thicknesses of about 0.6 microns to about 3 microns) are, among other things, that the smaller ceramic fibers have higher strength, higher toughness, and higher flexibility (e.g., each of which is important for improved mechanical stability during battery cycling), higher levels of surface smoothness achievable in the separator layer (e.g., stand-alone separator membrane or separator coating) (e.g., important for reduced stress concentrations and thereby improved mechanical stability during battery cycling), smaller pore size (thus providing more robust protection against accidental internal shorts or penetration by small particles), and smaller membrane thickness (thus providing faster ion transport and higher cell-level energy density).
[0047] In some designs, it may be advantageous (e.g., for improving cell stability or increasing cell assembly yield, among other benefits) for the individual small ceramic (e.g., oxide) fibers (or flakes) within the separator membrane layer to exhibit an average tensile strength in the range of about 50 MPa to about 50 GPa (e.g., in the range of about 100 MPa to about 50 GPa), in some designs about 0.5 GPa to about 50 GPa.
[0048] In some designs, it may be advantageous for such ceramic-containing separator layers (e.g., stand-alone separator membranes or separator coatings) to further include about 0.1-50 wt. % of a polymer, or about 0.01-50 wt. % of another type of ceramic particles of various shapes and sizes (hereafter referred to as "secondary" ceramic particles), or both (e.g., to improve mechanical properties, or to shut down the cell upon overheating, or for improved anode adhesion or improved electrochemical stability, etc.). In some designs, the polymer composition or secondary ceramic particle composition may be disposed in a separate, separate layer within such separator layers (e.g., stand-alone separator membranes or separator coatings). In some designs, the ceramic-based separator layers may be prepared as stand-alone membranes, while in other designs, the ceramic-based separator layers may be realized as a coating on at least one electrode (e.g., anode or cathode or both), or may be used as both a membrane and a coating for optimal performance (e.g., best reliability). In some designs, the ceramic-based separator layer may be realized as a coating on one or both sides of a polymeric separator membrane (e.g., an aramid separator membrane). In some designs, one electrode may be coated with one type of separator layer (e.g., a polymeric separator layer, or a separator layer including one type / composition of ceramic material or one size distribution or aspect ratio distribution of ceramic material or one shape of ceramic material, or a separator layer including a mixture of one type of polymer and one type of ceramic material or a mixture of ceramic materials including bonded or porous particles, etc.) and the other electrode may be coated with another type of separator layer (e.g., a separator layer including another type / composition of ceramic material or a mixture of ceramic materials or another size distribution or aspect ratio distribution of ceramic material or another shape of ceramic material, or a separator layer including a different polymer / ceramic mixture, etc.) to achieve desired performance characteristics.For example, in some designs, improved performance may be achieved based on different sizes of particles in the electrodes, or based on different requirements for electrochemical stability of the anode and cathode, or based on the advantage of matching or controlling the mechanical properties of different layers to reduce or prevent the formation of cracks or defects that could cause cell failure, based on the suppression of different side reactions on the electrodes, and / or based on other reasons.
[0049] In some designs, the electrodes can be coated with polymeric, ceramic, or hybrid polymeric / ceramic nanoparticles (of various shapes and sizes) to further level and flatten the electrodes. In some designs, such coatings can be deposited before a further coating with a layer containing small ceramic (e.g., oxide) fibers or small ceramic flakes. As an illustrative example, a self-leveling dispersion (e.g., with a target average thickness of about 3 pm) can be coated onto an electrode with a known thickness of about 80 pm (one side) and a maximum particle (or agglomerate) size of about 10 pm to achieve an electrode with a thickness variation of less than + / - about 1 pm. In some designs, the wet thickness can be adjusted to ensure that surface defects are substantially covered (buffed out) by the separator layer coating.
[0050] Depending on the particular application and membrane composition, in some designs, suitable porosity in a separator layer (e.g., a stand-alone separator membrane or a separator coating) may range from about 5 vol.% up to about 99.9 vol.% (more preferably, about 20.0 vol.% to about 85.0 vol.%), with higher porosity being desirable for thicker separator membranes or for applications requiring faster ion transport.
[0051] In some designs, a porous, flexible ceramic separator layer (e.g., a stand-alone separator membrane or separator coating) may include small fibers, at least some of which are bonded to each other (e.g., locally sintered or bonded to each other locally by chemical (primary) bonding or by using ceramic or polymer or hybrid ceramic / polymer bonding layers) and / or to other types of particles (e.g., low aspect ratio flakes or particles). In some designs, such bonds may include secondary bonds (e.g., hydrogen bonds or van der Waals bonds) in addition to or instead of chemical bonds. Although individual hydrogen bonds or van der Waals bonds are significantly weaker (exhibiting lower bond energy) than individual chemical bonds, they offer the great advantage of being able to repair and improve new secondary bonds (after being broken). In contrast, broken chemical bonds are often irreparable or difficult to repair. The large contact area between fibers (or differently shaped flakes or particles) involving hydrogen bonds and high density secondary bonds may compensate for the low strength of individual secondary bonds in some designs, resulting in very strong overall bonds between adjacent particles (e.g., fibers, flakes, etc.). In some designs, a porous, flexible ceramic separator layer (e.g., a stand-alone separator membrane or separator coating) may include small flakes, at least some of which are bonded to each other (e.g., locally sintered or bonded to each other locally by chemical bonding or by using ceramic or polymer or hybrid ceramic / polymer bonded layers) and / or bonded to other types of particles (e.g., low aspect ratio fibers or particles). In some designs, such bonds may include hydrogen bonds or van der Waals bonds in addition to or instead of chemical bonds.In some designs, the porous, flexible ceramic separator layer (e.g., a stand-alone separator membrane or separator coating) can include both small flakes or small fibers, at least some of which are bonded to each other (e.g., locally sintered or locally bonded to each other by chemical bonds or by using ceramic or polymer or hybrid ceramic / polymer bonded layers). In some designs, such bonds can include hydrogen bonds or van der Waals bonds in addition to or instead of chemical bonds. In some designs, the porous, flexible ceramic separator layer (e.g., a stand-alone separator membrane or separator coating) can include fibers or flakes of different sizes. In some designs, it can be advantageous for the average bond strength (e.g., average tensile strength) of the bonded areas (between individual fibers or flakes or between particles of different shapes) to range from about 0.01% to more than about 100.0% (e.g., about 1% to more than about 100%) of the average strength (e.g., average tensile strength) of the individual small fibers (or small flakes). Higher bond strengths are generally advantageous to achieve high strength of the membrane. In some designs, some small fibers (or small flakes) may be used in combination with other (e.g., even smaller) fibers (or flakes) that exhibit substantially larger diameters or thicknesses (e.g., 3-50 times) or substantially larger lengths (e.g., 3-1,000 times) or substantially larger aspect ratios (e.g., 3-1,000 times) or substantially different (e.g., 3-1,000 times) elasticity (maximum strain) or stiffness (elastic modulus) or substantially different (e.g., about 2 to about 1,000 times) bending radii to achieve desirable mechanical properties. In some designs, it may be advantageous for the separator membrane layer strength (e.g., in both tensile and compressive tests) to be in the range of about 1.0 MPa to about 2,000.0 MPa (in some designs, about 10.0 MPa to about 500.0 MPa). Higher strength may help reduce layer thickness as well as cell fabrication defects during assembly. Additionally, higher strength may improve the robustness of the cell during operation.Good bonding between individual fibers (eg, small fibers) can help achieve such strength values.
[0052] In some designs, small fibers (or small flakes) may be used in combination with larger fibers (e.g., fibers with diameters greater than about 1 micron and less than about 10 microns) or larger flakes (e.g., flakes with average thicknesses greater than about 0.6 microns and less than about 3 microns) to improve membrane properties or manufacturability. In some designs, at least some of the small fibers (or small flakes) are attached to larger fibers (or large flakes). Such an arrangement may allow for improved mechanical stability in some designs. In some designs, the fibers may be entangled. In some designs, the aspect ratio of at least some of the fibers (e.g., about 0.1-100%) may be greater than 100. In some designs, the length of at least some of the fibers (e.g., about 0.1-100%) may exceed one or more average linear dimensions (e.g., average diameter) of the active electrode particles. In some designs, the length of at least some of the fibers (e.g., about 0.1 to 100%) may exceed one or more average linear dimensions (e.g., average diameter) of the active electrode particles by about 2 to about 20,000 times.
[0053] In some designs, it may be advantageous to fabricate and utilize a porous, flexible ceramic separator layer (e.g., a stand-alone separator membrane or separator coating containing small fibers) with a sufficiently low bending radius. Such parameters may depend on the mechanical properties of the membrane (e.g., bond area and strength between fibers, average fiber length, etc.), porosity, level of fiber entanglement, membrane thickness, and the specific requirements may depend on whether the separator is stand-alone or in the form of a coating on an electrode or another membrane, cell assembly technique, cell size and shape (e.g., cylindrical vs. pouch cells), and / or other parameters. In some designs, it is preferable to achieve and utilize separator layers with minimum bending radii in the range of about 0.005 cm to about 20 cm (in some designs, about 0.1 mm to about 3 cm, and in other designs, about 0.2 cm to about 2 cm).
[0054] A typical calculation unit of a battery cell generally includes the unit area of half the anode current collector foil, one side of the anode coating, the separator layer, one side of the cathode coating, and one half of the cathode current collector foil. In some designs, the porous, flexible ceramic separator layer deposited (as a coating) on either one electrode (or both electrodes) or one (or both) surfaces of the separator membrane may include small fibers or small flakes that are not strongly bonded to each other or to larger fibers or flakes using strong chemical bonds. Instead, in some designs, the small fibers or small flakes may be bonded to each other or to larger fibers or flakes using electrostatic or van der Waals forces or hydrogen bonding, or by using small amounts (e.g., about 0.01-30 wt%) of a polymeric binder. In some designs, when the electrodes grow in a lateral dimension during cycling, small fibers or flakes within such layer or layers can advantageously move relative to one another without forming cracks or other undesirable defects that can cause cell failure. In some designs, the use of two or more separator coatings in the computational units of a battery cell (e.g., one on the cathode and one on the anode, or one on the separator and one on the cathode, or one on the cathode, one on the anode, and a third on the separator, etc.) can be advantageous in reducing the probability of formation of internal short circuits, improving the yield of high quality cells, and improving cell robustness.
[0055] In some designs, it may be advantageous for the standalone separating coating layer comprising small ceramic (e.g., oxide) fibers or small flakes to exhibit a thickness in the range of about 3.0 microns to about 60.0 microns (in some designs, about 5.0 microns to about 15.0 microns). For example, a film that is too thick may reduce the energy and power density of the battery to undesirably low levels, while a film that is too thin may be difficult to handle, achieve high cell production yields, and prevent defects during cell operation (e.g., formation of internal short circuits, etc.).
[0056] As mentioned above, in some designs, at least one (or both) of the electrodes may be coated with a separator layer. In some designs, there may not be an additional stand-alone separator membrane used in the cell. In some designs, the fabrication process for such a separator layer may require the formation of a stable dispersion of small ceramic (e.g., oxide) fibers (or flakes or other suitable particles). In traditional cell construction, stand-alone sheets of polymeric separator are fabricated and sold in large rolls to cell manufacturing facilities. These sheets are either divided into the form factor of the desired cell structure or kept as sheets that are rolled into a multi-layer cell. In some designs, a coatable dispersion of small ceramic (e.g., oxide) fibers (or flakes or other suitable particles) may be possible to coat directly onto the surface of the electrode while it is still on the roll (e.g., by using a roll-to-roll process). In some designs, the formation of a suitable separator coating layer may allow for a reduction in the volume fraction of inactive materials within the cell (e.g., because such layers may be constructed thinner than a stand-alone separator; e.g., advantageously having a thickness of about 0.5 microns to about 5.0 microns), further simplifying cell construction and reducing cell fabrication costs. In some designs, a variety of polar solvents may be effectively utilized in the formation of suitable dispersions of small ceramic (e.g., oxide) fibers (or flakes or other suitable particles). Suitable examples of such solvents include, but are not limited to, water, various alcohols (ethanol, methanol, acetone, propanol, and many others), various glycols, various glycol ethers, various ethers, N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), methyl ethyl ketone (MEK), hexamethylphosphoramide, cyclopentanone, acetonitrile, tetramethylene sulfoxide, e-caprolactone, and many others (depending on the polymer application, available equipment, cost, and other factors).In some designs, a suitable viscosity of the dispersion (colloid) of small ceramic (e.g., oxide) fibers (or flakes or other suitable particles) may range from about 1 to about 10,000 cp (e.g., depending on the coating method used) and can be adjusted by adjusting the solids content and / or weight percent of additives. In some designs, the high tensile strength requirements established for traditional stand-alone separators (established to allow processing of wound rolls of separator membrane) may be significantly reduced or even eliminated entirely. In some designs, a suitable dispersion may also include a polymeric binder or a surfactant or both. For example, such a polymer may help to create a more uniform dispersion of the small fibers (or small flakes or small particles) and achieve better mechanical properties. In some designs, a plasticizer may be used in conjunction with the polymer to improve the coating properties of the separator. In some designs, a suitable percentage of the polymeric binder in the final coating layer may range from about 0 to about 50 weight percent (e.g., about 0.5 weight percent to about 50 weight percent). In some designs, suitable porosity of the final coated separator layer may range from about 10% to about 90% by volume (e.g., more preferably, from about 25% to about 80% by volume). In some designs, such coated separator layers may be deposited using pre-metered coating means (e.g., spray coating or slot die (or gravure) coating methods, etc.) or self-metered coating means (e.g., dip coating, roller coating, knife edge coating, among others). In some designs, the coating layer may be advantageously deposited using solvent-free (solvent-less) methods. Examples of such suitable coatings may include, but are not limited to, magnetic assisted impaction coating, supercritical fluid spray coating, electrostatic coating, dry powder coating, photocurable coating, to name a few. In some designs, it may be advantageous to heat treat the coating layer prior to final cell assembly.Suitable heat treatment temperatures may range from about 40 to about 200°C, depending on the composition of the coating and the battery chemistry. Such treatment may improve the adhesion and mechanical properties of the coating, aid in the removal of undesirable contaminants, or advantageously redistribute polymeric components (if present) in the coating. In some designs, it may be advantageous not to calendar the electrodes after depositing the separator coating (e.g., to prevent the formation of undesirable defects, or for other performance, stability, or cost benefits).
[0057] It should be noted that suspension compositions containing small fibers (or small flakes) for the preparation of coated separator layers as disclosed herein may also be effectively used for the preparation of stand-alone membranes. Similarly, the same or similar methods may also be used for the preparation of stand-alone membranes as described herein for the preparation of coated separator layers.
[0058] In some applications (e.g., in some air filtration or some liquid filtration, or in some membranes used in energy storage (e.g., Li-ion batteries) or energy conversion (e.g., fuel cells) applications), the separation layer described herein may be deposited on another standalone or supported membrane (e.g., a membrane with larger pores or that may exhibit better mechanical properties). As mentioned above, in some designs, at least one side of a standalone battery separator membrane may be coated with small ceramic (e.g., oxide) fibers (or flakes or other suitable particles) as well. Such separator coatings may include polymers and may be used in combination with coatings of at least one electrode to enhance cell safety. In some designs, a roll-to-roll application system may be utilized for the separator membrane coating.
[0059] In some designs, slot die coating may be particularly advantageously used to form a separator layer coating (e.g., on the surface of one or both electrodes) from a suitable dispersion of small ceramic (e.g., oxide) fibers and other suitable particles or mixtures thereof. In some designs, this dispensing process may be particularly beneficial in situations where the electrode surface is imperfect. For example, if the surface of the electrode is known to have significant thickness variation (e.g., + / - about 1 pm or + / - about 3 pm), that uncertainty may be added to the target thickness of the separator. In this way, valleys of the electrode may be filled and peaks of the electrode may have an additional buffer of the separator layer. Furthermore, since small fibers may have length dimensions on the same order as the uncertainty of the electrode coating, in some designs dispensing a coating of such fibers at a thickness of the desired thickness of the separator plus twice the uncertainty of the coating layer will generally be sufficient to cover any peaks.
[0060] As noted above, in some designs, ceramic-based separator layers (e.g., stand-alone separator membranes or coatings) for energy storage applications are impregnated with a liquid or solid (at operating temperatures) electrolyte when used in a device to provide excellent strength, fracture resistance, outstanding thermal stability, low coefficient of thermal expansion, relatively high dielectric constant, low cost, scalable manufacturability in thin geometries (e.g., up to about 0.1-0.5 microns in some designs), good wettability with a wide range of materials, stability against reduction at low constant potentials (e.g., on the order of about 0 V vs. Li / Li+ for aluminum oxide) and against oxidation at high potentials (e.g., on the order of about 10 V vs. Li / Li+), and low dendrite resistance. Resistance to the growth of gallium ions and / or other beneficial properties of the disclosed films can be obtained that make the ceramic-based separator layers (e.g., stand-alone separator membranes or separator coatings) particularly attractive in a wide range of energy storage applications, including, but not limited to, energy storage devices based on various metal ions (e.g., Li-ions, Na-ions, Mg-ions, etc.) (e.g., batteries, including Li and Li-ion batteries, Na and Na-ion batteries, Mg and Mg-ion batteries, electrochemical capacitors, hybrid devices, etc.), to name a few.
[0061] In some designs, it may be advantageous to deposit a layer of another material on the surface of small ceramic (e.g., oxide) fibers (or flakes). This may be for desirable modification of mechanical properties, modification of dielectric properties, modification of interfacial properties (e.g., interfacial energy, strength, wetting angle, tribological properties, etc.), modification of optical properties, protection from undesired side reactions, and / or other reasons. In some designs, suitable surface layer thicknesses for the other material may vary from as thin as a submonolayer (e.g., a discontinuous monolayer with an average thickness in the range of about 0.01-0.2 nm) to as thick as about 1.00 pm (1 micron). In one example, an average layer thickness in the range of about 0.3 nm to about 30 nm may be preferred for many applications.
[0062] Depending on the application, the surface layer of the small ceramic fibers (or flakes) can be polymeric, carbon, dielectric, or ceramic materials. Examples of suitable ceramic surface layers include, but are not limited to, various oxides, various chalcogenides (e.g., sulfides) and oxychalcogenides, various halides (e.g., fluorides) and oxyhalides, various nitrides and oxynitrides, various carbides and oxycarbides, various borides, mixtures thereof, and the like. In some applications, the surface layer of the small ceramic fibers (or flakes) can also be advantageous to form a composite surface layer coating. In some applications, the surface layer of the small ceramic fibers (or flakes) can also be advantageous to form a porous coating layer. In some designs, the pores of the coating layer can be filled with another functional material. In some applications, the coating layer can leave closed pores in the porous oxide fibers. In some applications, these closed pores can be filled (pre-filled) with another functional material. In some applications, the pores can be open. In some applications, the coating layer may include one or more closed and filled (pre-filled) pores, along with one or more open pores (or surface pores).
[0063] In some applications, it may be advantageous to place two or more layers of material as a surface coating on small ceramic fibers (or flakes). These layers may differ in composition, density, porosity, surface chemistry, mechanical or optical properties, and / or other substantial differences. For example, an inner layer of the coating may have smaller pores, while an outer layer of the coating may be pore-free, thus forming closed pores within the small fibers or flakes. Such pores may be advantageously filled with another useful material (e.g., electrolyte additives) that can diffuse out of the membrane during operation of the device (e.g., Li-ion battery).
[0064] In some designs, different methods may be suitable for forming the surface layer. These include, but are not limited to, conversion and deposition reactions that take place in gas or liquid environments, and combinations thereof. Examples of suitable deposition methods in the gas phase include, but are not limited to, various types of chemical vapor deposition (CVD) (including plasma-enhanced deposition), atomic layer deposition (ALD), physical vapor deposition (PVD, e.g., sputtering, pulsed laser deposition, thermal evaporation, etc.), and various combinations thereof. CVD and ALD may be preferred for some applications that require more conformal and more uniform (and relatively economical) deposition. Examples of suitable liquid phase deposition include, but are not limited to, electrodeposition, plating, electrophoretic deposition, layer-by-layer deposition, sol-gel, chemical solution deposition or chemical bath deposition (CSD or CBD), etc.
[0065] In some designs, some synthesis techniques are particularly advantageous for forming small diameter ceramic fibers (or small flakes) suitable for separator layer (eg, stand-alone separator membrane or separator coating) compositions.
[0066] In some designs, techniques for the synthesis of small diameter ceramic fibers and flakes include catalyst-assisted chemical vapor deposition (CVD), cylindrical template-based synthesis, hydrothermal synthesis, electrospinning, forming small rolls from platelets, etc. In some applications, such techniques may suffer from high cost and low yields (especially in the case of CVD, electrospinning, and hydrothermal synthesis at high pressure). Moreover, the small fibers and small flakes produced by such techniques may be difficult or expensive (or unsafe) to incorporate into separator layer (e.g., standalone separator membrane or separator coating) compositions.
[0067] In contrast, according to at least one embodiment of the present disclosure, small ceramic fibers (and / or small ceramic flakes) produced by certain techniques may be particularly advantageous for use in forming suitable ceramic separator layer (e.g., stand-alone separator membrane or separator coating) compositions. Additionally, in some designs, it may be advantageous to incorporate small ceramic fibers (or flakes) produced via different techniques.
[0068] One exemplary technique for forming small ceramic fibers (or flakes) is by controlled oxidation of one or more molten metals or one or more metal alloys. In one example, small metal oxide fibers can be produced by controlled oxidation of liquid aluminum or aluminum alloys, or liquid magnesium or magnesium alloys (in some designs, by using certain additives to these aluminum or magnesium alloys, such as vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, selenium, sulfur, silicon, germanium, tellurium, cerium, praseodymium, neodymium, cerium, promethium, samarium, europium, gadolinium, gallium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and the like, among others). Small ceramic fibers produced by this technique can exhibit diameters ranging from about 3 nm to about 20 nm and very high aspect ratios (e.g., in the range of about 50 to about 500,000), with diameters of up to about 0.01 cm. 3 / g ~ approx. 1cm 3 / g range of total open pore volume between small ceramic fibers (e.g., including the open pore volume of individual fibers, such as surface pores, as well as any intervening pore space sandwiched among the fibers, when disposed in a ceramic-containing separator layer). In some synthetic designs, the length of ceramic (e.g., oxide) fibers produced by such techniques may be greater than about 1 cm, and in some cases even greater than about 10 cm (in some special cases, the length may even exceed about 100 cm). Furthermore, in some designs, such small ceramic fibers (e.g., aluminum oxide fibers) may have an overall volume of less than 1 cm. 3 or about 1000cm 3 or (in some cases) approximately 1,000,000 cm 3The separator may be fabricated in bulk (as large blocks or aggregates) that may exceed 100 nm. Thus, in some designs, these bulk pieces of weakly bonded small fibers may be broken apart and processed to produce a suitable separator layer (e.g., a stand-alone separator membrane or separator coating). In some designs, small ceramic (e.g., oxide) fibers may be produced by controlled oxidation of one or more solid metal alloys of one or more suitable compositions at a suitable temperature (e.g., where no passivating oxide layer is formed and the material is energetically favorable during the oxidation process to convert to a fibrous form). Another exemplary technique for the formation of small ceramic fibers (or flakes) may include the intermediate formation of small organometallic fibers (e.g., metal alkoxide fibers, such as aluminum ethoxide or lithium-aluminum-ethoxide or aluminum-magnesium ethoxide or aluminum-magnesium-lithium ethoxide, among others), followed by their conversion to small ceramic (e.g., oxide) fibers. The intermediate formation of such small organometallic fibers may be effectively used for the fabrication of small porous ceramic (e.g., oxide) fibers with controlled porosity and crystallinity (such fibers may, for example, be made X-ray amorphous or produced as polycrystalline with grains of controlled size). In some designs, the formation and use (in membranes) of small fibers that are amorphous (or polycrystalline with an average grain size in the range of less than about 20.0 nm, e.g., between about 0.5 nm and about 20.0 nm) may be particularly attractive (e.g., these amorphous or nanocrystalline fibers may be less brittle and exhibit higher strength or other beneficial properties).In an illustrative example, such techniques include (i) forming one or more suitable bimetallic alloys (e.g., Al-Li, Mg-Li, Al-Mg-Li, etc.) of one or more suitable compositions (e.g., lithium-containing metal alloys with a Li content ranging from about 4 atomic % to about 50 atomic %), (ii) exposing such one or more bimetallic alloys to one or more suitable solvents (e.g., suitable alcohols such as ethanol, isopropanol, etc.) to preferentially dissolve the more reactive metal (e.g., Li from Al-Li or Mg-Li or Al-Mg-Li alloys) and simultaneously form small organometallic fibers of the less reactive metal (e.g., Al or Mg or multi-metal alkoxides such as ethoxides, isopropoxides, methoxides and other related compounds, etc.) while preventing passivation of the less reactive metal, and (iii) exposing the small organometallic fibers to an oxygen-containing environment (e.g., dry air) to dissolve the small organometallic fibers into small oxide fibers (e.g., aluminum oxide (e.g., Al), which may be porous. 2 O 3) or magnesium oxide (e.g., MgO) or composite aluminum-magnesium oxide or composite aluminum-lithium oxide or aluminum-magnesium-lithium oxide or other oxides, etc. In some approaches, small alkoxide (e.g., ethoxide) fibers may be formed from alkoxide (e.g., ethoxide) powders via solution growth in alcohol (e.g., ethanol) at elevated temperatures (e.g., 50-200° C.). In some designs and applications (e.g., when used in Li-ion battery separators), small oxide (or oxyhydroxide or oxyfluoride or oxynitride or, more generally, oxygen-containing) fibers or small oxide (or oxyhydroxide or oxyfluoride or oxynitride or, more generally, oxygen-containing) flakes may advantageously contain about 2.0 atomic % to about 50.0 atomic % aluminum (Al) atoms (e.g., in some designs, about 2.0 atomic % to about 40.0 atomic % aluminum (Al) atoms). In some designs and applications (e.g., some filters and certain battery types), it may be advantageous for the small oxide (or, more generally, oxygen-containing) fibers or small oxide (or, more generally, oxygen-containing) flakes to contain from about 0.1 atomic % to about 35.0 atomic % silicon (Si) atoms.
[0069] In some synthesis approaches, the small organometallic fibers produced may form agglomerates (flocks) that can be at least partially separated (exfoliated) into individual fibers or smaller flocks by heat treatment in a solvent (e.g., an alcohol, e.g., ethanol, methanol, propanol, isopropanol, etc.) at temperatures ranging from about room temperature to about 200° C. (depending on the specific chemistry and solvent properties, including vaporization points and vapor pressures at different temperatures). In some designs, the small oxide fibers produced may contain significant amounts of residual lithium (e.g., about 0.01-20 atomic %), which forms lithium-aluminum oxide or lithium magnesium oxide or lithium aluminum magnesium oxide, among other suitable compositions. In some designs for Li-ion batteries, the presence of such Li may be advantageous for cell stability. In some synthesis designs, water or an aqueous solution of the desired pH (e.g., basic) may be used in place of one or more solvents to form metal hydroxide, metal, or metal oxide fibers. In some synthesis designs, the organometallic fibers may be at least partially converted to hydroxide fibers prior to conversion to oxide (or other ceramic) fibers. In some designs, the small ceramic fibers produced via the above synthesis processes may exhibit average diameters ranging from about 20 nm to about 2,000 nm (depending on synthesis conditions) and high aspect ratios (e.g., from about 20 to about 100,000 in one example, and from about 50 to about 100,000 in another example). In some synthesis designs, the length of the ceramic (e.g., oxide) fibers produced via the above synthesis processes may exceed about 10 microns. In some synthesis designs, the length of the small ceramic (e.g., oxide) fibers produced via the above synthesis processes may exceed about 1 mm. In some designs, the small ceramic (e.g., oxide) fibers may form large aggregates or blocks (bulk pieces) when separated from the solvent and dried.
[0070] Another preferred exemplary technique for the formation of small ceramic fibers (or flakes), also involving the intermediate formation of small organometallic (precursor) fibers (e.g., alkoxide precursor fibers), is based on blow spinning (e.g., melt spinning or solution spinning) of organometallic (precursor) fibers and their subsequent conversion to oxide (or other ceramic) fibers (including porous fibers) by heat treatment in a controlled gaseous environment (e.g., dry air or an oxygen-containing environment). In some designs, the conversion from the processor to oxide (or other ceramic) fibers may occur during blow spinning if the process is carried out at high temperature and in a suitable (e.g., oxygen-containing) gaseous environment. In some designs, flame pyrolysis may be effectively utilized. In some designs, polymers and / or other materials may be added to the blow-spun precursor solution to control its viscosity, (nano)fiber morphology, and porosity of the final product (small fibers). In some designs, the polymers may be burned or oxidized in the final product (small fibers) or removed (at least partially) in other ways.
[0071] In some designs, a dispersion of small ceramic (e.g., oxide) fibers (or small or large flakes) produced via the synthesis process described above (or by other suitable synthesis processes) may be formed by taking one or more blocks (or one or more bundles or one or more aggregates) of small ceramic fibers (or small or large flakes), adding a solvent (e.g., alcohol or water, etc.), and then using physical agitation (e.g., milling, sonication, ultrasonication, various other mixing techniques, etc.) to break up the bundles and allow the individual small ceramic fibers or flakes (or small bundles of less than about 10-20 fibers or flakes) to float freely in the solvent. In some designs, the bundles can be broken up and the individual small ceramic fibers or flakes can be extracted by heating to high temperatures (e.g., about 50-200° C.) and exposure to high pressures (e.g., about 1-1000 atm.). In some designs, a surfactant can be added to achieve a better (e.g., more stable or containing a larger portion of individual fibers or flakes) suspension.
[0072] In some designs, blocks (bulk pieces) of small as-produced ceramic (e.g., oxides such as aluminum oxide or magnesium oxide or other suitable oxides) fibers (or flakes) may be physically or chemically bonded to one another in a manner that is substantially weaker than the chemical bonds that form the atomic structure of the material into the fibers (or flakes). Such weak bonds between individual fibers or flakes may be severed using a suitable form of mechanical processing without significantly damaging (or at least excessively damaging) the individual fibers or flakes. Examples of suitable mechanical processing include, but are not limited to: ball milling (including high impact or high energy ball milling), shaker milling, planetary milling, roller milling, agitator bead mill, sonication, and ultrasonic processing. In some examples, the length of the as-produced individual ceramic fibers (or flakes) may be too long to form a stable suspension and / or be used in a separator membrane or separator coating layer. Although the optimal length of the individual ceramic fibers (or flakes) will depend on the particular application, the particular solvent and the particular characteristics of the designed separator layer (e.g., a stand-alone separator membrane or separator coating) or other factors, the maximum small fiber length (or maximum small flake diameter) will rarely exceed 500 microns when produced according to the synthesis process described above. In some designs, suitable conditions for the formation of stable dispersions of small ceramic (e.g., oxides such as aluminum oxide or magnesium oxide or other suitable oxides) fibers (especially having particles produced by oxidation of a metal or alloy melt) or flakes (especially flakes having a thickness of less than about 50 nm) are described below.
[0073] Figure 2 shows a standalone Al 2 O 3 An example image of a nanofiber separator membrane 201 is shown. The membrane in this example is Al 2 O 3It was prepared by coating a nanofiber dispersion onto a substrate, drying the coating and removing it from the substrate. 2 O 3 Nanofiber dispersions were prepared by suitable wet milling conditions using as-prepared Al 2 O 3 It was prepared from a block (bulk piece) of nanofibers.
[0074] Figure 3 shows the Al alloy produced by oxidation of the aluminum alloy melt. 2 O 3 An example of a cross-sectional scanning electron microscope (SEM) micrograph of a separator membrane 301 made from nanofibers is shown. The membrane in this example is Al 2 O 3 Nanofiber dispersion was prepared, and Al 2 O 3 Nanofiber dispersions were prepared by suitable wet milling (milling in a liquid medium) conditions using as-prepared Al 2 O 3 It was prepared from a block (bulk piece) of nanofibers.
[0075] In some designs, the milling conditions (e.g., speed, size or diameter of media, mass of media, vessel shape, type of milling, etc.) can affect the dispersion characteristics (e.g., final aspect ratio and final size distribution of small fibers or small bundles thereof, etc.).
[0076] In some process designs, a roller mill can be used to disperse the bulk of small fibers (or flakes) to achieve a final fiber (or flake) aspect ratio of greater than 10,000. In some examples, a roller mill can be used to disperse the bulk of small fibers (or flakes) to achieve a final aspect ratio of greater than about 5,000. In some examples, a roller mill can be used to disperse the bulk of small fibers (or flakes) to achieve a final aspect ratio of greater than about 1,000.
[0077] In some process designs, the bulk of the small fibers (or flakes) can be placed in a (e.g., cylindrical) vessel along with milling media and solvent. Various examples of milling media quality, solvents, and milling conditions are described below. In some examples (especially for particles produced by oxidation of metal or alloy melts), the diameter of the milling media can be selected between about 0.01 cm and about 0.1 cm. In some examples, the diameter of the milling media can be selected between about 0.1 cm and about 1 cm. In some examples, the diameter of the milling media can be selected between about 1 cm and about 5 cm. In some designs, milling media of different sizes (e.g., diameters) and / or compositions can be combined to achieve the most desired dispersion. In some designs, the optimal size (e.g., diameter) of the milling media can depend on the dimensions and characteristics of the fibers (or flakes), the speed of mechanical agitation, the size of the vessel, the density of the milling media, and / or other conditions. For example, if the milling media diameter is too small (e.g., less than about 0.01 cm), it may result in a non-uniform mixture of small fibers (or flakes) with a wide distribution of aspect ratios, and / or bundles of fibers (or flakes) that are not completely separated and dispersed. Such dispersions may have poor coating quality, particularly non-wetting to the substrate, non-uniform coating thickness, and macroporosity (empty spaces of broken films in the coating). Separator films or membranes made from dispersions with poor coating quality may have weak fracture and tensile strength, may be prone to shorting during cell fabrication or cycling, and may exhibit poor ion transport properties. On the other hand, if the milling media is too large, the resulting dispersion may consist of many bundles of wires with large aspect ratios, since media with diameters much larger than the width of the nanowires may not be able to interact efficiently. Such dispersions may create coating films or separator membranes with poor surface uniformity and microporosity (empty spaces between large fiber bundles of undesirably large size).Films made from dispersions with poor coating quality will have weakened fracture and tensile strength and are prone to short circuits.
[0078] In some process designs, it may be advantageous to combine multiple media sizes in the milling of small ceramic fibers (or flakes) and / or use multiple milling stages with different size media, or more broadly, to use a variety of milling conditions (which may include using different solvents, different media, different milling energies and speeds, etc.) In some designs, it may be advantageous to mill small ceramic fibers (or flakes) through multiple stages that include different types of agitation (e.g., combining different milling types, or combining milling with sonication (or ultrasonication) in one or more stages).
[0079] In some process designs, the solvent used in the milling process may be water. In some designs, the solvent used in the milling process may be an alcohol with a carbon chain size ranging from 1 to 5 carbons, or from 6 to 10 carbons. In some designs, the optimal size of the alcohol molecule (e.g., to achieve the most stable dispersion with the greatest percentage of individual small fibers or flakes or flakes / fibers of the desired size) may be influenced by multiple parameters due to their effect on the dipole moment. In some designs, the solvent may be a glycol or glycol ether. In some designs, surfactants or other additional solvents or additional salts (which may include organic or inorganic salts) may be added in small or moderate amounts (e.g., about 0.00001% to about 20% by volume) to improve the quality of the dispersion or to induce doping of small fibers at a later stage in the preparation of the membrane (or coating) (e.g., to induce localized sintering or bonding between fibers or flakes, etc.). In some designs, fibers of different sizes (or batches) may contain different additives. In some designs, these batches are mixed together prior to electrode / separator coating or membrane formation. In some designs, special doping of individual batches or fibers (or flakes) of different composition may induce bonding between binders from different batches without inducing (e.g., with heat treatment) comparable bonding between fibers (or flakes) of the same batch. In some designs, additives may be added after the dispersion or milling process. If additives are used in the dispersion / milling process, the choice of solvent may be influenced by the compatibility of the solvent with the additive. In one example, the effect of the dipole moment of the solvent may affect the flocculation (aggregation) time of particles (e.g., fibers or flakes) of a given size.
[0080] In some designs, suitable milling media materials include yttria (Y 2 O 3 ) stabilized zirconia oxide (YZT), corundum (Al 2 O 3), steel, tungsten carbide, etc. In some designs, the milling media material can have a large effect on the properties of the dispersion. For example, if the media is not dense enough, it may not have enough inertia to break up and disperse large bundles of nanowires at a given milling speed. Conversely, if the density of the milling media is greater than desired, it can cause fiber (or flake) fracture perpendicular to its "long axis", resulting in particles with undesirable small aspect ratios.
[0081] In some designs, one or more polymers (which in some designs include a plasticizer) and / or one or more surfactants can be added to the slurry during milling to aid in the formation of stable colloids containing individual small fibers (or flakes) or agglomerates of only a relatively small number of small fibers or flakes (e.g., about 2 to about 2,000).
[0082] In some examples, a suitable loading of small ceramic (e.g., oxide) fibers (or flakes) in the milling vessel can be about 0.01 to about 1 weight percent of the total dispersion (e.g., flakes / fibers + media + solvent + additives) mass. In some examples, a suitable loading of small ceramic (e.g., oxide) fibers (or flakes) in the milling vessel can be about 1 to about 10 weight percent of the total dispersion mass. In some designs, if the weight percent is too high, milling may take too long or the media may not affect the small fibers (or flakes) in the desired manner required to create a substantially uniform and stable dispersion. Additionally, in some designs, the loading of small fibers (or flakes) may have a direct effect on the final viscosity of the dispersion, which may be a critical parameter for the quality of the final separator coating (or separator membrane). For example, if the weight percent is too low, the milling media may unnecessarily wear too much due to media-media impacts / interactions during milling, resulting in a lower than desired dispersion viscosity. In some examples, the milling media loading in the milling vessel can be about 1 to about 50 weight percent of the total mass / weight of the mixture (flakes / fibers, solvent and additives). In some examples, the milling media loading in the milling vessel can be about 50 to about 100 weight percent of the total mass / weight of the mixture (flakes / fibers, solvent and additives). In some examples, the milling media loading in the milling vessel can be about 100 to about 200 weight percent of the total mass / weight of the mixture (flakes / fibers, solvent and additives). In some examples, the milling media loading in the milling vessel can be about 200 to about 300 weight percent of the total mass / weight of the mixture (flakes / fibers, solvent and additives). In one example, if the weight percent of the milling media is too low, milling may take a very long time or the media may not affect the nanowires in the desired manner required to create a substantially uniform and stable dispersion. Additionally, in one example, the amount of milling media added can have a direct effect on the final viscosity of the dispersion, which can be a critical parameter for the quality of the final separator film / membrane.On the other hand, in one example, if the weight percentage of media is too low, the milling media may suffer excessive wear from media-to-media impacts and the viscosity of the dispersion may be lower than desired.
[0083] In some designs, the rotation speed of the milling vessel can have a significant effect on the quality of the dispersion and can depend on the size and density of the milling media, the density and mechanical properties of the small fibers (or flakes), the difference in density between the fibers and the solvent, the size of the milling vessel, and / or other parameters. In some examples, a suitable rotation speed of the milling vessel can be between about 50 and about 100 rpm. In some examples, a suitable rotation speed of the milling vessel can be between about 100 and about 200 rpm. In some examples, a suitable rotation speed of the milling vessel can be between about 200 and about 300 rpm. In some examples, a suitable rotation speed of the milling vessel can be between about 300 and about 400 rpm. In some examples, a suitable rotation speed of the milling vessel can be between about 400 and about 600 rpm. In some examples, a suitable rotation speed of the milling vessel can be between about 600 and about 2000 rpm. In some examples, a suitable speed of the milling vessel can be between about 0.3 and about 1 m / sec. In some examples, a suitable speed of the milling vessel may be between about 1 and about 2 m / s. In some examples, a suitable speed of the milling vessel may be between about 2 and about 3 m / s. In some examples, a suitable speed of the milling vessel may be between about 3 and about 6 m / s. In some examples, a suitable speed of the milling vessel may be between about 6 and about 14 m / s. In some designs, if the rotation speed of the milling vessel is too high, the resulting dispersion may contain small fibers with unnecessarily low aspect ratios (e.g., down to nearly spherical nanoparticles). In some designs, separator layers (e.g., standalone separator membranes or separator coating films) made from such undesirable dispersions may be prone to embrittlement and cracking, may have reduced mechanical properties such as weakened fracture and tensile strength, and may be prone to short circuits (e.g., during secondary processing and / or cycling). In one example, if the rotational speed of the milling vessel is too slow, the mill rotational speed may not impart enough energy to the media to break up large bundles of fibers (flakes), and the resulting dispersion may consist of a heterogeneous mixture of small fibers (or flakes) with an unnecessarily wide distribution of aspect ratios.Such dispersions can produce films with poor surface uniformity and microporosity (e.g., unnecessarily large sized open spaces between large fiber bundles). Separator layers (e.g., standalone separator membranes or separator coating films) made from such undesirable dispersions can exhibit poor quality (e.g., weakened fracture and tensile strength, and prone to short circuits during cell construction or operation). In some examples, suitable milling times can range from about 10 to about 30 minutes. In some examples, suitable milling times can range from about 30 to about 60 minutes. In some examples, suitable milling times can range from about 60 to about 120 minutes. In some examples, suitable milling times can range from about 120 to about 240 minutes. In some examples, suitable milling times can range from about 240 to about 480 minutes. In some examples, suitable milling times can range from about 480 minutes to 5 days.
[0084] At the end of the milling procedure, the resulting milled product (e.g., a milled mixture of small ceramic fibers or flakes and solvent and / or additives) may be characterized as a slurry. In some examples, a suitable final slurry viscosity may range from about 50 to about 500 centipoise. In some examples, a suitable final slurry viscosity may range from about 500 to about 1000 centipoise. In some examples, a suitable final slurry viscosity may range from about 1000 to about 2000 centipoise. In some examples, a suitable final slurry viscosity may range from about 2000 to about 10,000 centipoise. In some designs, when creating a stable functional dispersion of ceramic small fibers (or flakes), the final slurry viscosity may be an important parameter that may be controlled by the milling media loading, the loading of small ceramic fibers (or flakes), the solvent composition, the additive composition, and / or the processing conditions. In some designs, the conditions described above that can be used to control the final slurry viscosity containing small ceramic fibers (or flakes) may be quite different than the conditions that can be used to create a dispersion of nanoparticles with a similar viscosity. In other words, a desirable dispersion may have a particular viscosity, but not all dispersions with a particular viscosity are desirable.
[0085] Milling media material, solvent, additives, milling media size, small fibers (e.g. Al 2 O 3 or MgO or ZrO 2 While there are many possible combinations of loadings of additives (e.g., fibers), milling speeds, and milling times, some such combinations can produce much better quality of the final separator layer (e.g., a stand-alone separator membrane or a separator coating) than other combinations.
[0086] In one illustrative example of a suitable slurry formulation, 8 g of bulk small Al produced by oxidation of an Al alloy melt was added to the slurry. 2 O 3The fibers were ground into approximately 0.05g pieces and placed in an 8 oz jar. Sixteen 1 / 2 inch diameter steel media were then added to the jar along with 200ml of ethanol and no additives (no salt or solvent additives). The sample was mixed on a roller and milled at 160 rpm for 12 hours to achieve a high quality dispersion with the desired uniformity, small individual fibers, and desired aspect ratio.
[0087] As mentioned above, in some designs, the optimal milling conditions to achieve good dispersion of bulk to small fibers (or flakes) may be significantly different from the optimal conditions for nanoparticles or larger particles. For example, in some designs, to obtain a dispersion of nanoparticles with an average size of about 100 nm, media of about 0.1 mm or less should preferably be used. Furthermore, in some designs, the milling speed and loading ratio should be further optimized for the type of particles being milled, as well as the solvent and milling time. In contrast, in some designs, it may be preferable to use media sizes of 1 mm or more to achieve a good dispersion (e.g., suitable for secondary processing of separator layers, e.g., as a standalone separator membrane or separator coating) of small fibers with a diameter of about 100 nm.
[0088] In the above example, it may be helpful to consider the dimensions of the material prior to milling. As an example, in a milling process, particles with dimensions of about 100 pm may be reduced in size by milling to an average longest dimension (e.g., fiber length or flake width) of about 10 pm using media of about 10 mm size. In the case of fibers, some designs may select the media size to target the largest dimension (length) of the fiber for size reduction. For example, if a fiber is about 100 pm long and about 100 nm in diameter, selecting a larger media diameter, such as about 10 mm, may preferentially reduce the fiber length in size to about 10 pm. Furthermore, in some designs, if nanofibers that are 100 pm by 100 nm are bundled into bundles about 100 pm wide, the nanofibers will be split by the milling media to a maximum size of about 10 pm, but the bundles may be preferentially broken down into single fibers of about 100 nm in diameter with an average length less than about 10 pm, so that most will be even smaller.
[0089] In some designs, the aspect ratio of the small fibers (or flakes) in the final dispersion (e.g., before forming a separator layer, such as a stand-alone separator membrane or separator coating) may preferably range from about 1:4 to about 1:1,000,000. In some examples, the aspect ratio may range from about 1:50 to about 1:500. In other examples, the aspect ratio may range from about 1:500 to about 1:5,000. In still other examples, the aspect ratio may range from about 1:5,000 to about 1:50,000. In some designs, the aspect ratio may affect the mechanical properties (including flexibility, strength, and toughness) and pore size distribution and density of the separator layer (e.g., a stand-alone separator membrane or separator coating). In some designs, it may be desirable to combine fibers of different sizes and different aspect ratios. In some designs, larger fibers may preferably exhibit a smaller average aspect ratio (e.g., about 2 times or about 4 times or more) compared to smaller fibers or small flakes (when flakes are used instead of or in addition to fibers). Similarly, in some designs, it may be advantageous to combine small fibers with small flakes (each with its own aspect ratio distribution), or larger fibers with small flakes (each with its own aspect ratio distribution), or small fibers with large fibers and additional flakes (each with its own aspect ratio distribution).
[0090] In one illustrative example, a dispersion of small fibers (e.g., average diameter about 5-8 nm) with an average aspect ratio of about 1,000 can be mixed with another dispersion of larger fibers (e.g., average diameter about 40-60 nm) with an average aspect ratio of about 250 in a weight ratio of about 2:1. This dispersion mixture can be characterized as having a bimodal aspect ratio distribution characteristic of the two parent dispersions. This mixed suspension can then be utilized in the preparation of an effective separator layer (e.g., a stand-alone separator membrane or a separator coating).
[0091] In another illustrative example, a dispersion of small fibers (e.g., average diameter between about 5-8 nm) having an average aspect ratio of about 1,000 can be mixed in a weight ratio of about 1:1 with another dispersion of larger fibers (e.g., average diameter between about 40-60 nm) having an average aspect ratio of about 150. This dispersion mixture can be characterized as having a bimodal aspect ratio distribution characteristic of the two parent dispersions. This mixed suspension can then be utilized in the preparation of another effective separator layer (e.g., a stand-alone separator membrane or a separator coating).
[0092] In yet another illustrative example, a dispersion of small fibers (e.g., average diameter between about 5-8 nm) with an average aspect ratio of about 1,000 can be mixed with another dispersion of small porous flakes (e.g., average thickness between 3-6 nm) with an average aspect ratio of about 200 in a weight ratio of about 4:1. This dispersion mixture can be characterized as having a bimodal aspect ratio distribution characteristic of the two parent dispersions. This mixed suspension can then be utilized in the preparation of another effective separator layer (e.g., a stand-alone separator membrane or separator coating).
[0093] In addition to flakes and fibers of various sizes, other types and shapes of particles or nanoparticles can be utilized in preparing separator layers (e.g., standalone separator membranes or separator coatings) in other embodiments of the present disclosure (e.g., nanostars, nanorings, planar and three-dimensional dendritic nanostructures, among others).
[0094] Returning to the use of additives for suitable dispersions, in addition to co-solvents and salts (both organic and inorganic salts), other types of additives can include, but are not limited to, (polymeric) binders, sintering agents, anti-agglomerating agents, thickeners, emulsifiers, electrostatic stabilizers, surfactants, anti-agglomerating agents, and / or other types of additives that can be added to the solvent (e.g., before making the dispersion) or to the dispersion itself to achieve the desired dispersion. Such materials are referred to as "additives" in this disclosure.
[0095] In one illustrative example, the additive (e.g., surfactant) may be added in an amount of about 2 wt % (based on the weight of both the solvent and the small fibers or flakes) prior to the agitation process (e.g., milling). In another illustrative example, two additives (e.g., a sintering aid in an amount of about 3 wt % (based on the weight of both the solvent and the small fibers or flakes) and a surfactant in an amount of about 2 wt % (based on the weight of both the solvent and the small fibers or flakes)) may be added once the dispersion is preformed. In yet another illustrative example, the additive (e.g., a surfactant in an amount of about 4 wt % (based on the weight of both the solvent and the small fibers or flakes)) may be added during application of the dispersion. In yet another illustrative example, the additive (e.g., a sintering aid) may be added after the dispersion is applied as a fine mist to a separator layer (e.g., a stand-alone separator membrane or separator coating) made from a dispersion of small fibers (or flakes). In one example, the one or more additives may also be sprayed onto the separator layer (e.g., a stand-alone separator membrane or separator coating) (or dried fibers or flakes), deposited onto the separator coating (or separator membrane), or introduced as a gaseous medium (vapor), among other methods of addition.
[0096] In some designs, when a standalone separator membrane is prepared from ceramic (e.g., oxides such as aluminum oxide, lithium aluminum oxide, magnesium oxide, aluminum-magnesium oxide, lithium magnesium oxide, lithium-aluminum-magnesium oxide, zirconium oxide, etc.) particles (small flakes, small fibers, etc.), it may be important to use one or a combination of various processing techniques to achieve good mechanical properties. One example of a suitable processing technique is to bond individual (e.g., randomly packed, mostly in-plane) small fibers or flakes together (e.g., by sintering, including pressure-assisted sintering or other means) in the final form to form a ceramic separator membrane. In some designs, when the dispersion includes a mixture of particles of various shapes and sizes (e.g., small and large fibers or small fibers and flakes, etc.), bonding can occur between particles of different types (e.g., in addition to bonding between particles of the same type). In some designs, the fibers (or flakes) bonded (e.g., by localized sintering) can ideally retain desirable bending and stiffness properties while increasing fracture and tensile strength, among other desirable properties. In some designs, oxide fibers or flakes (e.g., small Al 2 O 3 One challenge in utilizing coarsening agents (fibers or flakes) is that without additives, such fibers (or flakes) may require high temperatures (e.g., greater than about 800° C.) to induce bonding together (e.g., via sintering) and may become unnecessarily coarse during the heat treatment process. Coarsening can cause undesirable reductions in porosity and flexibility, and can increase brittleness and fracture toughness. Thus, in some designs, it may be desirable to utilize anti-coarsening agents to achieve bonding (e.g., sintering) at lower temperatures where substantial coarsening does not occur, or to reduce (minimize) coarsening at higher temperatures.
[0097] In some designs, suitable additives may take the form of alkali hydroxides (e.g., LiOH, NaOH, KOH, etc.). Such hydroxides can be converted to oxides upon heating, and smaller oxides (e.g., Al 2 O 3 , MgO, ZrO 2 (e.g., SiO2) can form a eutectic with the fibers (or flakes), thereby allowing for lower sintering temperatures. In some designs, such additives are introduced into a dispersion (suspension) of fibers (or flakes) or into a preformed separator layer (e.g., a stand-alone separator membrane or separator coating) and heat treated at a temperature high enough to provide adequate mobility, but low enough to induce conversion to an oxide that is primarily located in the areas where adjacent fibers (or flakes) contact one another.
[0098] In some designs, the separator membrane may be initially formed not from small, elongated ceramic (e.g., oxide) particles of suitable shape and size (e.g., small fibers or small flakes, etc.), but rather from small, elongated particles (e.g., small fibers or large fibers or small flakes, or mixtures thereof, etc.) of an organometallic compound (e.g., a metal alkoxide such as an aluminum alkoxide such as aluminum ethoxide, among others).
[0099] In one illustrative example, a small amount of a concentrated solution of LiOH in one solvent ("solvent A") (in this example, anhydrous butanol) can be added to a suspension of small aluminum (or magnesium or other suitable metal) alkoxide (e.g., aluminum ethoxide or magnesium isopropoxide, etc.) fibers (e.g., about 50-100 nm in diameter) dispersed in another solvent ("solvent B") (in this example, anhydrous ethanol). The mixture is then coated onto a substrate to form a thin (e.g., about 20 microns thick) film. If a dry film remains, the hydroxide and alkoxide phases can be converted to oxide phases by heating the sample in an oxidizing environment (e.g., dry air) at high temperatures (e.g., about 300-1100 °C).
[0100] In some designs, it may be advantageous to use a mixture of ceramic (e.g., oxide) particles of suitable shape and size (e.g., small fibers or small flakes, etc.) and particles of suitable shape and size (e.g., small or large fibers or small flakes, etc., or mixtures thereof) of an organometallic compound (e.g., a metal alkoxide such as an aluminum alkoxide such as aluminum ethoxide, among many others) to form a separator layer (e.g., a separator coating or a stand-alone separator membrane). In the case of a membrane, heat treatment of the deposited membrane in a controlled environment softens the organometallic particles (e.g., small alkoxide fibers), while the ceramic particles (e.g., small oxide fibers) help the mixture retain the desired shape. Heat treatment can then bond the small oxide fibers to the small alkoxide fibers, which in turn bond (interlock) the alkoxide fibers to one another. Further heat treatment of the membrane in an oxidizing environment can convert the alkoxide to an oxide that forms an oxide membrane with desired properties (e.g., sufficient strength, flexibility, porosity, etc.). Similar additives can be used for mixtures of alkoxides and oxides as well as for pure oxide particles (e.g., fibers, flakes, etc.).
[0101] In some designs, suitable additives include alkali nitrates (especially LiNO 3 , NaNO 3 , KNO 3 , CsNO 3etc.), which may decompose and react with ceramic (e.g., oxide) or organometallic (e.g., alkoxide) fibers or flakes or other particles in the original dispersion. In one illustrative example, a small amount of a concentrated solution of lithium nitrate in solvent A may be added to a solution of aluminum alkoxide (in this example, ethoxide) nanowires dispersed in solvent B. The mixture is then coated onto a substrate to form a thin film (e.g., about 5-100 microns), dried, and heat treated (e.g., at about 300-800°C). In this example, solvent A is an anhydrous alcohol such as, but not limited to, butanol, and solvent B is an anhydrous alcohol such as, but not limited to, methanol. If a dry film remains, the nitrate and alkoxide phases may be converted to oxide phases by heating the sample in an oxidizing environment.
[0102] In some designs, suitable additives can take the form of alkali alkoxides, including LiOR, NaOR, KOR, CsOR, where R is an alkane containing 1 to 10 carbon atoms.
[0103] In some designs, it may be advantageous to add lithium alkoxide (e.g., to aluminum or magnesium alkoxide) to small alkoxide fibers (or flakes) in various organic solvents to control the relative solubility of the alkoxides (e.g., to allow precipitation of the Li alkoxide within small metal alkoxide fibers for later use as a sintering agent). In one illustrative example, a small amount of a concentrated solution of lithium alkoxide in solvent A may be added to a solution of small aluminum alkoxide fibers dispersed in solvent B. The mixture is then coated as a thin film (e.g., about 3-50 microns) on a substrate. If the vapor pressure of solvent B is higher than that of solvent A, the lithium alkoxide will begin to precipitate as solvent B evaporates, nucleating at the junctions of the aluminum alkoxide nanowires where the most surface area is available. In this example, solvent A can be an anhydrous alcohol such as butanol or another suitable solvent, and solvent B can be an anhydrous alcohol such as methanol or another suitable solvent.
[0104] In some designs, after adding suitable additives, small ceramic (e.g., oxide) or organometallic (e.g., alkoxide) fibers (or flakes or other suitable particles) can be heat treated (and bonded, e.g., sintered, where most of the fibers will be bonded to at least one adjacent particle, such as an adjacent fiber of a flake) to form a mechanically robust porous membrane. In some synthesis designs, at least a portion of the organometallic (e.g., alkoxide) fibers (or flakes or other suitable particles) (e.g., in the membrane) can be at least partially converted to hydroxide or oxyhydroxide fibers (or flakes or other suitable particles) prior to conversion to ceramic (e.g., oxide) fibers (or flakes or other suitable particles). In some designs, such intermediate phases can help bond these fibers (or flakes or other suitable particles) to form a mechanically robust porous membrane with desirable flexibility and porosity. In some designs, box furnaces, tubular furnaces, belt furnaces, induction heaters or other devices can be utilized for heat treatment. Depending on the application, the appropriate processing temperature is Al 2 O 3 For the formation of a separator membrane, the processing temperature may range from about 100° C. to about 1100° C., and for the formation of a MgO separator membrane, the processing temperature may range from about 100° C. to about 2000° C. For other types of ceramic separator membranes, suitable processing temperatures may range from about 100° C. to about 2000° C. In some illustrative examples, the maximum heat treatment temperature may be from about 200° C. to about 300° C., from about 300° C. to about 400° C., from about 400° C. to about 500° C., from about 500° C. to about 600° C., from about 600° C. to about 700° C., from about 700° C. to about 800° C., from about 800° C. to about 900° C., from about 900° C. to about 1000° C., or from about 1000° C. to about 1100° C. In some designs, the sintering temperature is preferably optimized to match the additive chemistry so that the melting point or chemical reactions (i.e., phase transformations or eutectic melts) that allow sintering of small (e.g., oxide) fibers occur at a lower temperature than would be required without the additive.
[0105] In some designs, it may be advantageous to modify the sintering atmosphere during heat treatment (e.g., to allow chemical reactions between additives and small ceramic (e.g., oxide) fibers at a desired temperature, or surface reactions between the small ceramic fibers). Examples of such atmospheres include, but are not limited to, nitrogen, argon, helium, hydrogen, water vapor (H 2 O) and oxygen gas or various mixtures thereof (e.g., volume fractions from about 0 to about 100%). In some designs, gaseous environments (e.g., H, 2 O) can significantly enhance the surface diffusion of species on the surfaces of small fibers (compared to bulk diffusion), so that bonding can occur at temperatures low enough that undesirable grain coarsening does not proceed at an unnecessarily fast rate.
[0106] In some approaches, reactive gases can apply heat to small ceramic (e.g., oxide) or organometallic (e.g., alkoxide) fibers (or flakes or other suitable particles). In some designs, the heating rate and the ratio of reactive to non-reactive gas flows (if a gas mixture is used) can be optimized for the most favorable film formation. In some designs, the ratio of reactive to non-reactive gases can range from about 0.1 to 0.990, and temperature ramp rates can generally range from about 0.1° C. / min to about 1000° C. / min, depending on the composition and chemistry of the mixture, the pressure, and the environment (e.g., air). Examples of reactive gases include, but are not limited to, CO. 2 , H 2 O, NH 4 OH, NH 3 , O 2 , H 2 , and N.F. 3 Examples of non-reactive gases include Ar, N 2 , and other precious metals.
[0107] In some designs, laser or plasma treatments can be used to induce bonds between small ceramic (eg, oxide) or organometallic (eg, alkoxide) fibers.
[0108] In some designs, mechanical (or hydrostatic) pressure (e.g., in the range of about 1 to about 50,000 atm.) can be advantageously applied during sintering (bonding) to increase the contact surface area between the fibers during the sintering (bonding) process. In some examples, such pressure can be applied by a hot press, gravity pressure, or negative pressure from a dynamic vacuum.
[0109] In some designs, heat applied to small ceramic (e.g., oxide) or organometallic (e.g., alkoxide) fibers (or flakes or other suitable particles) may use a specific ramp rate during one or more heating stages for most favorable film formation. For example, suitable ramp rates may generally range from about 0.1° C. / min to about 1000° C. / min, depending on the composition and chemistry of the mixture, the pressure and the environment (e.g., air).
[0110] In some designs, the polymer separator may contain oxide particles incorporated within the pores or on one of its surfaces. In these examples, the main function of the polymer separator is to electrically isolate the anode and cathode, while the oxide particles are added to provide an extra level of safety at high temperatures where the polymer membrane may shrink and break. Unfortunately, the overall thermal stability of such composite membranes may be quite poor, the adhesion of the particles to the membrane may not be very good (e.g., ceramic particles may fall off the membrane during handling), and the overall thickness of such composite membranes is generally quite large (e.g., within about 1-30 microns in some designs and about 15-30 microns in others).
[0111] One or more embodiments of the present disclosure provide for the addition of one or more polymeric additives that primarily serve as improved mechanical support or as binders that bind (or help bind) small ceramic (e.g., oxide) fibers (or other suitable particles such as flakes or mixtures thereof) together (or, in some designs, with an electrode or another membrane). In such designs, the addition of the polymer improves the mechanical properties (e.g., strength, flexibility, adhesion, fracture toughness, etc.) of the separator membrane or separator membrane layer that includes the small fibers. In some designs, the addition of the polymer to the membrane can reduce or prevent electrochemical reduction of small ceramic (e.g., oxide) fibers (or other suitable particles such as flakes or mixtures thereof) when the separator membrane is in direct contact with the anode at potentials where electrochemical reduction would typically occur. For example, an anode containing lithium or graphite or Sn or Si in a Li-ion battery can be exposed to sufficiently low potentials that can induce undesirable electrochemical reduction of oxide (or ceramic) fibers in direct contact therewith, which can lead to irreversible Li loss. In some designs, a thin layer of polymeric binder between the anode and the membrane or the addition of a small amount of polymeric binder to the membrane can prevent such undesirable results.
[0112] In some designs, at least a portion of the polymeric component of the membrane (including small ceramic (e.g., oxide) fibers or other suitable particles such as flakes or mixtures thereof) may be in the form of polymeric fibers (including porous fibers and small fibers) or polymeric flakes (including small and porous flakes) or composite fibers or composite flakes with polymer. Such polymeric fibers (or flakes) may bond or / and entangle with the small ceramic fibers (flakes) to improve the mechanical properties or processability of the separator membrane. Due to the high elasticity (and deformability) of the polymeric component, the polymeric component may help to form bonds with the ceramic particles over a larger contact area, thus increasing the overall strength of the membrane. Moreover, in some designs, the polymeric component may increase the overall elasticity of the membrane and the overall toughness of the membrane. In some designs, the polymeric component (e.g., fibers or flakes) may help to form a more stable suspension of the ceramic particles to form a more uniform separation layer. In some designs, the polymeric fibers or flakes may have smaller dimensions or aspect ratios than the ceramic fibers or flakes (e.g., the polymeric fibers or flakes may range from about 1 nm to about 200 nm in diameter or thickness). In some designs, the smaller diameter of the polymeric fibers may result in a higher proportion of chemical groups (compared to the total mass of the polymer), which may further allow the polymeric fibers or flakes to be more easily deformable (e.g., bending around ceramic particles) and thus form more bonds with the ceramic particles. Moreover, small polymeric fibers (or flakes) may exhibit higher (normalized to cross-sectional area) strength (compared to larger polymeric fibers or flakes). At the same time, larger fiber dimensions may result in higher fiber strength in absolute terms and thus be advantageous in some designs. Thus, in other designs, the polymeric fibers or flakes may have larger dimensions or aspect ratios than the ceramic fibers or flakes (e.g., diameter or thickness in the range from about 200 nm to about 10 microns).Still other designs may be advantageous to utilize a combination of polymeric fibers (or flakes) of different sizes, or to utilize polymers in both fiber (flake) and non-fiber (e.g., as particles with lower aspect ratios or random shapes, or as coatings, etc. In some designs, the polymeric fibers or flakes may form primary (chemical) bonds with the ceramic particles in the membrane. In other designs, the polymeric fibers or flakes may form secondary bonds with the ceramic particles (the advantages of which have been discussed above). Depending on the application and dimensions of the ceramic particles, the aspect ratio of the polymeric fibers or flakes may range from about 10 to about 10,000,000.
[0113] In some designs, it may be advantageous for individual polymeric flakes or fibers to exhibit tensile strengths in the range of about 10 MPa to about 10 GPa. In some designs, it may be advantageous for polymeric flakes or fibers to exhibit thermal stability in the range of about 120° C. to about 400° C. Examples of polymeric fibers (or nanofibers) with such thermal and mechanical properties include, but are not limited to, various cellulose fibers (or nanofibers), various chitin fibers (or nanofibers), various aramid fibers (or nanofibers), among many others.
[0114] In some designs, it may be advantageous for individual polymeric flakes or fibers to contain functional groups for primary or secondary bonding with ceramic fibers (including small fibers) or flakes (including small flakes).
[0115] In some designs, it may be advantageous for the ceramic-containing separator layer to exhibit a tensile strength (measured in air at room temperature) in the range of about 1 MPa to about 1,000 MPa. In some designs, it may be advantageous for the ceramic-containing separator layer to exhibit a tensile strength in the range of about 1 MPa to about 1,000 MPa within the operating temperature range (the specific temperature range will vary depending on the application; in some designs, it may range, for example, from as low as -70°C to as high as +200°C).
[0116] In some designs, it may be advantageous for the ceramic-containing separator layer to exhibit a room temperature tensile strength in the range of about 1 MPa to about 1,000 MPa when immersed in an electrolyte or electrolyte solvent mixture.
[0117] In some designs, it may be advantageous for the ceramic-containing separator layer to exhibit a compressive strength (measured in air at room temperature) in the range of about 1 MPa to about 2,000 MPa. In some designs, it may be advantageous for the ceramic-containing separator layer to exhibit a compressive strength (measured in air at room temperature) in the range of about 1 MPa to about 2,000 MPa over the operating temperature range (the specific temperature range will vary depending on the application; in some designs, it may range, for example, from as low as -70°C to as high as +200°C).
[0118] In some designs, it may be advantageous for the ceramic-containing separator layer to exhibit a room temperature tensile strength in the range of about 1 MPa to about 1,000 MPa when immersed in an electrolyte or electrolyte solvent mixture.
[0119] In some designs, it may be advantageous for the ceramic-containing separator layer to exhibit a room temperature compressive strength in the range of about 1 MPa to about 2,000 MPa when immersed in an electrolyte or electrolyte solvent mixture.
[0120] In some designs, the ceramic-containing separator layer has a permeability of approximately 1 L / m at 200 Pa, depending on the application and the supporting electrode or membrane (if present). 2 seconds ~ approx. 50,000L / m 2 It may be advantageous for the membrane to exhibit an air permeability (pressure difference across the membrane) of 0.1 to 0.5 mm. Higher air permeability may be advantageous for high rate applications in batteries and supercapacitors.
[0121] In some designs, it may be advantageous for the ceramic-containing separator layer to exhibit a pore exclusion size of about 1 micron or less (e.g., about 10 nm to about 1,000 nm), i.e., even if larger pores are present in the separator layer, they are connected only by submicron pores, so that particles larger than, for example, 1 micron (or a particular pore exclusion size) cannot penetrate the membrane.
[0122] As previously mentioned, polymer ceramic membranes may be advantageously heat treated (including heat treatment under pressure) at temperatures ranging from about 40 to about 300° C. (depending on the polymer composition and properties such as glass transition temperature, decomposition temperature, thermal expansion, etc.) to enhance the mechanical properties or purity of the membrane. In some designs, polymer-containing composite membranes containing small ceramic (e.g., oxide) fibers (or other suitable particles such as flakes or mixtures thereof) may include composite fibers containing both smaller ceramic (e.g., oxide) fibers and one or more polymers. In some designs, the percentage of such composite fibers in the separation membrane may range from about 1 to about 100% by weight. Such composite fibers (including small composite fibers) may be produced by a variety of spinning techniques, such as blow spinning, electrospinning (e.g., melt spinning or solution spinning), and more traditional spinning techniques (e.g., wet spinning, dry jet spinning, dry spinning, etc.). Such methodologies may rely on the formation of a polymer-small fiber-solvent colloid, or (e.g., in the case of melt spinning) the formation of a polymer-small fiber melt. In one example, blow spinning and electrospinning can produce much smaller diameter composite fibers (up to 10 nm, where the small ceramic fibers are 10 nm or smaller). During spinning, in some designs, the majority of the small ceramic fibers may be oriented parallel to the length of the fiber.
[0123] The relative weight, distribution and volume fraction of the polymers in various (e.g., as described above) polymer-small ceramic fiber (or polymer-small ceramic flake or, more generally, polymer-ceramic particle) composite films determine their thermal, physical and chemical properties and can be optimized for a particular application. For example, a higher percentage of the polymer component can result in lower polarity, lower thermal stability, higher thermal expansion, lower strength, higher flexibility, higher maximum elongation, higher processability, and lower oxidative stability. In another example, a higher percentage of small ceramic (e.g., oxide) fibers (or flakes or other suitable particles) can result in better electrolyte wettability, higher average dielectric constant, surface dipole and electrostatic interactions with the particles, higher mechanical strength (especially in compression), higher wear resistance, lower coefficient of thermal expansion, and / or better thermal stability. In a further example, the highest fracture toughness or toughness factor of such films can be achieved for some optimal weight fraction of the components (depending on the processing conditions, size, properties and shape of the small ceramic fibers, properties and shape of the polymer component, bonding between the polymer and the ceramic particles, contact area between the polymer and the ceramic particles, etc.). Overall, in some designs, the appropriate amount of polymeric component (or binder) in the separator membrane (based on the total weight of the ceramic polymer) generally ranges from about 0.0 wt.% to about 80.0 wt.% (depending on the preparation conditions and the desired separator membrane properties, depending on the application). Depending on the processing conditions, an excessive proportion of polymeric component can cause reduced membrane permeability and porosity, reduced wettability by the electrolyte, and reduced thermal stability, among other undesirable membrane properties.
[0124] In some designs of polymer-ceramic composite membranes, small ceramic (e.g., oxide) fibers (or other suitable particles such as flakes or mixtures thereof) can provide most of the electrical isolation between the anode and cathode, while one or more polymeric additives can still provide some increased electrical isolation between the anode and cathode. In one example, a relatively small weight percent of added polymer (e.g., about 0.1-20 wt.%, based on the total weight of the dry composite membrane) can be intended to bond the small ceramic (e.g., oxide) fibers (or other suitable particles such as flakes or mixtures thereof) at their junctions or to the electrode layer itself to better accommodate changes in size of one or more electrodes during cycling. In some examples (e.g., when the membrane is prepared from a dispersion), the polymeric binder can be added to the dispersion of small ceramic (e.g., oxide) fibers (or flakes or other particle types) at a loading of about 0.001-0.01 wt.% (based on the total mass of the oxide fibers or other oxide particles and solvent). In other examples, the binder may be added to the small fiber dispersion at a loading of about 0.01-0.1 wt % (based on the total weight of the oxide fibers or other oxide particles and solvent), and in still other examples, the binder may be added to the dispersion at a loading of about 0.1-50 wt % (based on the total weight of the oxide fibers or other oxide particles and solvent). The relative percentage of small ceramic (e.g., oxide) fibers in the polymer-ceramic composite membrane may be fairly broad, ranging from about 5 wt % to about 99.9 wt %. In some designs, the polymer component may also help achieve a uniform distribution of the ceramic particles within the membrane layer. In some designs, the polymer component may form primary (chemical) bonds with the ceramic particles. In other designs, the polymer component may form secondary (e.g., hydrogen or van der Waals) bonds with the ceramic particles. In some designs, there may be both primary and secondary bonds between the polymer component and the ceramic particles.
[0125] In some cases (depending on the particular application, synthesis method, and desired properties), the polymeric component of the composite polymer-small ceramic fiber (or polymer-small ceramic flake, or more generally, polymer-ceramic) film may include thermoset or thermoplastic polymers (standalone or as a mixture or as a co-polymeric component), including, but not limited to, various polysaccharides and mixtures of polysaccharides with other polymers, including, but not limited to, proteins (e.g., arabinoxylan, gum arabic, xanthan gum, among others). gum), pectin, chitin and chitin derivatives, various modified natural polymers, such as cellulose and cellulose derivatives, especially cellulose derivatives, including cellulose acetate (CA), cellulose acetate butyrate (CBA), carboxymethylcellulose (CMC), cellulose nitrate (CN), ethylcellulose (EC), alginates, including alginic acid and its salts; acrylonitrile-butadiene-styrene (ABS); allyl resin (Allyl); casein (CS); cresol-formaldehyde (CF); chlorinated polyethylene (CPE); chlorinated polyvinyl chloride (CPVC); various epoxies (polyepoxides), including fluorinated epoxies; epichlorohydrin copolymers (ECO); ethylene-propylene-diene terpolymers (EPDM); ethylene-propylene copolymers (EPM); ethylene-vinyl acetate copolymers (EVA); ethylene-vinyl alcohol (E / VAL);Various fluoropolymers (e.g. polytetrafluoroethylene (PTFE), polytetrafluoroethylene (PCTFE), perfluoroalkoxy polymers (PFA / MFA), fluorinated ethylene-propylene (FEP), tetrafluoroethylene, hexafluoropropylene, vinylidene fluoride and their copolymers (e.g. THV), polyethylene tetrafluoroethylene (ETFE), polyethylene chlorotrifluoroethylene (ECTFE), various perfluoroelastomers (FFPM / FFKM), chlorotrifluoroethylene vinylidene fluoride (FPM / FKM), tetrafluoroethylene propylene (FEPM), perfluoropolyethers (PFPE), perfluorosulfonic acid (PFSA), perfluoropolyoxetanes, polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), various fluorosilicone rubbers (vinyl, methyl, etc.)); various ionomer-thermoplastic polymers; isobutene-isoprene copolymers (IIR); various liquid crystal polymers (LCP); melamine formaldehyde hydride (MF);natural rubber (NR);phenol-formaldehyde plastics (PF);polyoxymethylene (POM);polyacrylates (ACM);polyacrylic acid (PAA);polyacrylamide, polyacrylonitrile (PAN);various polyamides (PA) (including various aromatic polyamides often called aramids or polyaramids);polyaryletherketones (PAEK);polybutadiene (PBD);polybutylene (PB);polybutylene terephthalate (PBTP);polycarbonate (PC);polychloromethyloxirane (epichlorohydrin polymer) (CO);polychloroprene (CR);polydicyclopentadiene (PDCP);polyester (in the form of thermoplastic or thermoset polycondensates);polyetheretherketones (PEEK);polyetherimides (PEI);polyethersulfones (PES);polyethylene (PE);polyethylenechlorinates (PEC);polyethyleneterephthalate (PET);Poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS);Phenol-formaldehyde (PF);Polyimide (PI) (as thermoplastic or thermosetting polycondensates);Polyisobutylene (PIB);Polymethylmethacrylate (PMMA);Polymethylpentene (PMP);Polyoxymethylene (POM);Polyketone (PK);Polymethylpentene (PMP);Polyethylene oxide (PEO);Polyphenylene oxide (PPO);Polyphenylene sulfide (PPS);Polyfutaramide (PTA);Polypropylene (PP);Propylene oxide copolymer (GPO);Polystyrene (PS);Polysulfone (PSU);Polyester urethane (AU);Polyether urethane (PUR);Polyvinyl alcohol (PV A); polyvinyl acetate (PVAc); polyvinyl butyral (PVB); polyvinyl chloride (PVC); polyvinyl formal (PVF); polyvinylidene chloride (PVDC); styrene-acrylonitrile copolymer (SAN); styrene-butadiene copolymer (SBR and YSBR); various silicones (SI) (e.g., polydimethylsiloxane, polymethylhydrosiloxane, hexamethyldisiloxane, Sylgard®, various silicone elastomers ((phenyl, methyl) (PMQ), (phenyl, vinyl, methyl) (PMVQ), (vinyl, methyl) (VMQ), etc.); polyisoprene; urea-formaldehyde (UF). In some designs, some such polymers may be at least partially fluorinated.;
[0126] In some designs, the polymers and copolymers of the composite polymer-small ceramic fiber membrane may include at least one of the following monomer components: acrylates and modified acrylates (methyl acrylate, methyl methacrylate, etc.), diallyl phthalates, dianhydrides, amines, alcohols, anhydrides, epoxies, dipodals, imides (polyimides), furans, melamines, parylenes, phenol-formaldehyde, polyesters, urea-formaldehyde, urethanes, acetals, amides, butylene terephthalates, carbonates, ether ketones, ethylene, phenylene sulfide, propylene, styrene, sulfones, vinyl, vinyl butyral, vinyl chloride, butylene, chlorobutyl, fluorobutyl, bromobutyl, epichlorohydrin, fluorocarbons, isoprene, neoprene, nitriles, sulfides, silicones, and the like, among others.
[0127] In some designs, silane coupling agents can be used to create strong bonds between polymers and ceramic (e.g., oxide) interfaces. These molecules have functional organic groups and functional silane groups (R-Si-X3, where R is an organic ligand and X is generally alkoxy, acyloxy, halogen, or amine) and therefore can link generally non-reactive surfaces. These groups can covalently bond or physically interact with polymers and inorganic (ceramic, such as oxide) surfaces. Examples of the three main structures of silane coupling agents include trialkoxysilanes, monoalkoxysilanes, and dipodal silanes. Bonding can proceed by hydrolysis of the silane group to generate hydroxy functional groups. The independent silane monomers can then be polymerized through a condensation reaction. The silicon-bonded hydroxy groups can then hydrogen bond to the hydroxy bonds of the inorganic substrate, followed by oxygen as crosslinks to the siloxane polymer. The organic functional groups can also be connected to siloxane polymers and serve as sites for organic molecules to bond chemically (e.g., covalently) or by secondary bonding / physical interactions (e.g., van der Waals, ionic interactions, hydrogen bonds, etc.). Anhydrous bonding may also be possible, where monomeric silane groups are covalently bonded to the inorganic substrate via oxane bonds. Monomer addition to the substrate may be able to produce a monolayer thin film of the silane coupling agent. Silane coupling agents can be used with polymers by treating the finished polymer or by including the silane coupling agent as a copolymer. Silane coupling agents can be used to modify resins by compounding or coating, or to surface treat fillers or ceramic particles.
[0128] In some designs, silane coupling agents can be used to obtain stronger linkages to inorganic (e.g., ceramic) and organic (e.g., polymeric) components in composite separator layer materials. Composite separator layers containing silane coupling agents can have improved mechanical stability, good thermal stability, higher ionic conductivity, and other improved properties. With the aid of silane coupling agents, a wider range of polymeric materials can also be made available that can be used with ceramics that are normally incompatible (or will not bond). In one example, ceramic materials (e.g., ceramic fibers or flakes) are functionally modified using silane coupling agents. Both hydrolytic (usually trialkoxysilanes, dialkoxysilanes) or anhydrous (monoalkoxysilane) covalent bonding can be used depending on the ceramic, precursor, and / or water sensitivity of the surrounding materials. This can be achieved by anhydrous liquid deposition (in one example, using a refluxing substrate containing about 5% silane coupling agent in toluene, tetrahydrofuran, and / or a hydrocarbon solution), aqueous alcohol deposition (in one example, about 95% EtOH / about 5% H2O, adjusted to a pH of about 5 mixture). 2This can be done using aqueous deposition (in one example, about 0.5-2.0% silane, about 0.1% non-ionic surfactant, adjusted to a pH of about 5.5), dip coating (in one example, by submerging the ceramic sample in a 2% silane solution for about 1-2 minutes), spray deposition (in one example, by spraying a 25% silane solution onto a ceramic powder or film), or vapor phase deposition (in one example, about 50°C to about 200°C at about 5-50 Torr). Dipodal silane may be used to increase the hydrolytic stability of the ceramic-polymer matrix. Alternatively, a silane coupling agent can be introduced as a monomer component of the copolymer to improve mechanical strength, thermal stability, and bonding ability. Some examples of silane coupling agents that can be used to crosslink ceramic composites include, but are not limited to: acrylate, methacrylate, aldehyde, amino, anhydride, azide, carboxylate, phosphonate, sulfonate, epoxy, ester, halogen, hydroxyl, isocyanate, masked isocyanate, phosphine, phosphate, sulfur, vinyl, olefin, polymeric, UV active, fluorescent, chiral, trihydro, dipodal, among other functional silanes.
[0129] In some designs, it may be advantageous for the composite membrane to utilize thermally stable polymers that maintain at least 50% of their room temperature tensile strength at elevated temperatures in the range of about 120.0° C. to about 450.0° C. in an inert environment or air (in some designs, such thermal stability temperatures may be desired to be greater than 150° C. or even 200° C.). In some designs, such polymers may advantageously include nitrogen (N) and / or fluorine (F) in their atomic composition. In some designs, the atomic fraction of N or F or both (N+F) may range from about 5 atomic % to about 70 atomic %. Illustrative examples of such polymers include, but are not limited to, Viton (chemical structure (C 3 F 6 ) n (C 2 H 2 F2 ) m ) and various polyimides, especially semi-aromatic and aromatic polyimides (e.g., polyimide (III) of pyromellitic anhydride and p,p'-diaminodiphenyl ether, poly-oxydiphenylene-pyromellitimide, among many others). In some designs, it may be advantageous to utilize side-chained or functionalized polyimides to bond with small ceramic fibers.
[0130] In some designs, it may be advantageous to expose the composite polymer-small particle (e.g., small ceramic fibers, small ceramic flakes, etc.) film to ultraviolet (UV) light at temperatures close to room temperature in a compatible atmosphere, which cures / crosslinks the polymer without compromising the polymer properties (in some cases simply in air, in an oxygen-containing environment) and improves the mechanical properties of the film.
[0131] In some designs, a metal salt or salt mixture (e.g., inorganic or organic or mixed) may be added to a suspension (dispersion) of small alkoxide or oxide fibers (e.g., flakes or other suitable particles or particle mixtures) prior to forming the separator membrane or prior to infiltrating the membrane after its preformation and drying. Such salts or salt mixtures may be of various anions (e.g., F - , Cl - , Br - , I - , NO 3 - , S.O. 4 - , CO 3 2- , C 2 O 4 2- , ClO 4 - , B.F. 4 - , P.F. 6 -and hydrated forms of these and other compounds). Examples of suitable organic anions of suitable salts include (but are not limited to) acetate and substituted acetates, 2-ethylhexanoates and substituted carboxylic acids, cyclopentadienides, substituted cyclopentadienides, cyclooctadienides, triphenylphosphines and substituted triphenylphonephines, acetylacetonates and substituted acetylacetonates, diketimines and substituted diketimines, bipyridines and substituted bipyridines, bis[1-N,N-dimethylamino)-2-propanolato (DMAP), acetonitrile dihalides, carbonyls and substituted carbonyls, cyclohexanes and substituted cyclohexanes, stearates and substituted stearates, porphyrins and substituted porphyrins, formates, acetates, and alkyl acetates, among others. Examples of suitable cations (or mixtures thereof) of salts include, but are not limited to, Al, arginine ... 3+ , Li + , Na + , Mg 2+ , Ca 2+ , Cr 3+ , Cr 4+ , Cr 5+ , Cr 6+ , K + , Zr 4+ , Zn 2+ , Sr 2+ , Ti 4+ , Sc 3+ , Fe 2+ , Fe 3+ , Cu 2+ , etc. In some designs, Rb + , Co 2+ Co 3+ , Ni 2+ , Mn + , Mn 2+ , Mn 3+ , Mn 4+ , Mn 5+ , Mn 6+ , Mn 7+ , Ta 3+ , Ta 4+ , Ta 5+ , Si 4+ , Ge4+ , La 3+ , V 5+ , V 3+ , Cs + , B.A. 2+ , Sr 2+ You can also use the following.
[0132] Such salts or salt mixtures can be dissolved in a compatible solvent prior to their addition. These metal salts can then be converted to oxides by exposure to UV light, bonding adjacent particles (e.g., small fibers or flakes) to form a robust, flexible separator layer (e.g., a stand-alone separator membrane or separator coating). In some examples, Ga(OR) 3 , Ti(OR) 4 , Zr(OR) 4 , V(OR) 5 , Ni(OR) 2 , CuOR, Zn(OR) 2 , LiOR, NaOR, KOR, Mg(OR) 2 , Ca(OR) 2 Metal alkoxides such as alkoxides can be added to dispersions of small ceramic (e.g., oxide) fibers and other particles and converted to the oxide by exposure to UV light and an oxygen-containing atmosphere (e.g., ambient atmosphere). The low temperature of this process makes it particularly attractive as it minimizes thermal stress and is compatible with heat-sensitive substrates (e.g., very attractive for forming separator layers as coatings on the surfaces of electrodes or separators).
[0133] In some designs, siloxane may be used as a bonding additive, which may be SiO 2 For example, O 2 UV light at 185 nm 3- is converted to O 3- can be photodissociated under exposure to 254 nm UV light to form molecular oxygen and atomic oxygen. The atomic oxygen then reacts with siloxanes (or metal alkoxides) to form SiO 2 (or metal oxide). In other designs, SiO 2The binders can be formed by gas phase chemisorption of organosilanes followed by photo-oxidation using 172 nm vacuum ultraviolet (VUV) light.
[0134] In some designs, small organometallic fibers (e.g., small alkoxide fibers) (or flakes or other suitable particles) or small hydroxide fibers (or flakes or other suitable particles) may be converted to oxide fibers (or flakes or other suitable particles) by exposure to ultraviolet light or ozone. In some designs, such exposure to UV light may induce bonding of randomly (or oriented) fibers (or flakes) with other adjacent fibers (or flakes) to produce a robust, flexible oxide film. In some designs, such small organometallic (or hydroxide) fibers (or flakes) may be mixed with oxide or other ceramic fibers (small or large) or flake-shaped particles (small or large) prior to UV exposure. In some designs, the fiber (or flake) dispersion (with or without additional salts) may be coated onto a substrate prior to UV exposure. In some designs, the fiber (or flake) coating may be dried prior to UV exposure. In some designs, the fiber (or flake) coating can be densified (e.g., by applying mechanical pressure, e.g., by calendaring) prior to UV exposure. In some designs, the fiber (or flake) coating can be heated (e.g., to a temperature ranging from about +30° C. to about 500° C. or higher) prior to UV exposure.
[0135] In some designs, the UV exposure may be performed at elevated temperatures, which may range from about +30° C. to about 1200° C. in some designs.
[0136] In some designs, the use of very thin (e.g., less than about 5-10 pm) and highly porous (e.g., porosity greater than about 75% of the total porosity) aluminum oxide (or other suitable oxide and suitable ceramic) membranes may enable a significant increase in the rate capability and energy density of Li and Li-ion batteries as well as other batteries while improving or maintaining the required level of safety. This level of porosity, which is beneficial for high rate capability, coupled with mechanical integrity and flexibility, may be achievable using small fibrous or flake-like structures. However, ceramic structures based on "ordered" (e.g., roughly spherical) particles, in contrast, require fairly dense packing to generate a mechanical network and are generally not very flexible. Because of their high stability at high potentials, such membranes can be used in Li and Li-ion battery cells in combination with high voltage cathodes (e.g., cathodes with average lithiation potentials of about 3.9 to about 5.6 V vs. Li / Li+).
[0137] In addition to using a stand-alone (e.g., porous aluminum oxide) separator membrane as described above, small fibers or flakes (e.g., made of aluminum oxide or porous aluminum oxide) can be deposited directly onto at least one of the electrodes (or onto another membrane) by using casting (e.g., slot die casting or blade casting), by spray deposition, by deposition with an electric field, by dip coating, or by another suitable method. In some designs, such deposited fibers can act as an integral (thin, flexible) membrane that provides low resistance to ion transport and separates the anode and cathode from direct electrical contact while occupying a relatively small space. In examples where the separator is manufactured by casting or spray drying from a dispersion, the separator can be dried (after casting / spray drying) at a temperature ranging from about 40°C to about 400°C.
[0138] FIG. 4 shows a small Al on electrode for producing a separator layer as a coating on the anode 402 of a Si-based Li-ion battery coated on a Cu foil 401. 2 O 3 An example of a fiber coating 403 is shown.
[0139] Figure 5 shows two small thickness Al films coated directly onto a high voltage lithium cobalt oxide (LCO) cathode and a Si anode. 2 O 3 A comparison of the performance characteristics of four full cells with Si-based Li-ion battery anodes constructed with one of the fibrous separators (thickSSAnode and thinSSAnode) and a conventional commercial polymeric (PP) separator (Control 4 and Control 5) is shown. All cells tested were constructed with identical anodes and cathodes. The capacity (mAh / g) is normalized by the weight of the anode coating. The mid-cycle hysteresis (V) was recorded when the cells were cycled at a C / 2 rate. The small Al 2 O 3 The lower hysteresis for the cells with the fibrous separator layer coating is clearly visible in FIG.
[0140] Al 2 O 3 In addition to separator layers (e.g., coatings or stand-alone membranes), other ceramic separator layers (including layers made from or including small fibers or flakes, including porous small fibers and flakes) can be utilized as separators in Li-ion and other batteries. These include MgO, ZrO 2 , various mixed oxides, etc. Important parameters in some designs are generally the mechanical properties, the stability of the ceramic membrane in the electrolyte, and (when in direct contact with the positive or negative electrodes) the absence of electrochemical side reactions (e.g., significant lithiation or dissolution in contact with the electrodes).
[0141] In some applications, stand-alone ceramics (Al 2 O 3 , MgO, ZrO 2 It may be advantageous to deposit a porous polymeric layer on one or both sides of the separator membrane (e.g., Li or Li-ion (or Na or Na-ion or other metal or metal-ion) battery). For example, when such a membrane is used in a Li or Li-ion (or Na or Na-ion or other metal or metal-ion) battery, undesirable side reactions (e.g., lithiation, electrochemical reduction, etc.) between the anode and the ceramic separator can be reduced or prevented by depositing such a porous polymeric layer (e.g., porous ethylene, porous propylene, porous aramid, porous cellulose, porous sugars, etc. - other examples of suitable polymers are described above) on the anode side of the membrane. Similarly, potential undesirable oxidation reactions can be reduced by forming such a porous polymeric layer on the cathode side of the membrane. In some designs, suitable thicknesses of such porous polymeric layers can range from about 10 nm to about 10 microns. In some applications of Li and Li-ion (or other metal or metal-ion batteries), it may be advantageous to deposit a thin (e.g., about 1 nm to about 200 nm), nearly non-porous (dense) polymer layer on the inner surface of the membrane (e.g., around the individual wires) to prevent direct contact of the ceramic wires with Li (e.g., in the case of Li dendrite formation). In some designs, it is even preferred that such a polymer layer is stable in contact with Li and exhibits high interfacial energy at the polymer / Li interface. In this case, the formation of Li dendrites would result in a large increase in the energy of the system, and their growth could be greatly reduced or eliminated. In contrast, direct contact of Li with many ceramic materials would result in the formation of a low energy interface, which would reduce the surface energy of the Li dendrites and thus unnecessarily favor their propagation.
[0142] In some applications, ceramics (e.g., Al 2 O 3 , MgO, ZrO 2It may be advantageous for the porous polymeric layer on one or both sides of the membrane to be thermally responsive (or include a thermally responsive layer) and close the pores above a certain temperature. This may provide an additional safety feature for the cell, as the membrane will block current flow above a certain temperature (e.g., selected in the range of about 70°C to about 120°C for some applications). In some designs, the thermally responsive layer may include a thermoplastic that melts above a critical temperature (e.g., selected in the range of about 70°C to about 120°C for typical applications) to block Li-ion conduction.
[0143] In some applications, it may be particularly advantageous (e.g., because of enhanced safety, which is particularly important for medium or large or extra-large cells) to use a separator layer (e.g., stand-alone separator membrane or separator coating) of oxide (e.g., aluminum oxide, magnesium oxide, zirconium oxide, etc.) or other suitable ceramic small fibers or flakes (including but not limited to porous small fibers or flakes) (e.g., in combination with a polymeric coating as discussed above) in medium-sized (e.g., about 10 mAh to about 200 mAh), large (e.g., about 200 mAh to about 10,000 mAh), or extra-large (e.g., greater than about 10,000 mAh) cells metal anode-based battery cells. Examples of suitable metal anode-based battery cells include, but are not limited to, cells with Li anodes (e.g., as in Li metal batteries), Mg anodes (e.g., as in Mg metal batteries), Na anodes (e.g., as in Li metal batteries), Zn anodes (many battery chemistries include Zn or Zn alloy anodes and electrolytes that do not induce dissolution or reduction of small wire films), K anodes (e.g., as in K metal batteries), to name a few. In some designs, rechargeable metal anode batteries may particularly benefit from this membrane technology. Metal anodes in such rechargeable battery cells may undergo metal stripping (dissolved as ions in the electrolyte) during discharge and re-plate during charging. This process may cause the formation of dendrites that may induce internal short circuits, which may cause battery failure (and in some instances, various safety risks such as fires, especially known for Li battery chemistries). The use of surface layer protection with solid electrolytes or solid ceramic protective layers is often expensive, is not always suitable and does not necessarily protect the cell from dendrite penetration (especially in situations where the battery may be subjected to shocks or various stresses, such as when used in transportation).In some battery research, it is common for the majority of scientists to utilize so-called half-cells (e.g. Li half-cells) with metallic anodes (usually very small coin-shaped cells with a capacity of less than about 10 mAh) to evaluate the performance of electrode materials or separators, but the use of metallic anodes in commercial cells (especially rechargeable cells with aqueous liquid and organic electrolytes) is rare due to the high cost of metallic anodes as well as reliability and safety concerns (larger cell sizes would result in more energy being released during dendrite-induced thermal runaway and rapid decomposition, especially when flammable organic electrolytes are used). The use of small fiber or flake separator layers (e.g., separator membranes or separator coatings) described herein (e.g., porous aluminum oxide or magnesium oxide or zirconium oxide membranes, to name a few) with relatively high elastic modulus of the membrane material, high porosity, and (potentially significant) small (e.g., less than about 2 microns on average, more preferably less than about 0.25 microns) tortuous pores can significantly reduce or eliminate dendrite growth while still allowing relatively fast metal (e.g., Li, Mg, Zn, etc.) deposition (plating) and thus high power density. Although metal dendrites can penetrate many polymer membranes in some applications (e.g., during metal dendrite growth in cells with polymer separator membranes), metal dendrites may not be able to penetrate individual small oxide fibers (e.g., small aluminum oxide fibers), even if these are coated with a polymer layer. Thus, in some applications, the formation of metal dendrites requires that the dendrites grow around small fibers, which can significantly increase the specific surface area of the dendrites. Small features of the membrane wall, its roughness, its dielectric properties, or its surface properties may also play a role in inhibiting dendrite growth.
[0144] In some designs, medium or large or extra large sized cells with other (non-metallic) anodes (e.g., Si-based or graphite-based) can also benefit greatly from the use of porous ceramic (e.g., flexible) small fiber (including but not limited to porous small fibers) or small flake separator layers (e.g., separator membranes or separator coatings) in their construction due to significantly improved safety, higher compressive strength, reduced ionic resistance, better thermal stability or other beneficial properties.
[0145] In some applications, the use of an ion-permeable (e.g., porous) polymer layer between a membrane containing small fibers or flakes (including, but not limited to, porous small fibers or flakes) of an oxide (e.g., aluminum oxide, magnesium oxide, zirconium oxide, etc.) and at least one electrode can be beneficial for use as a separator in an electrochemical cell (e.g., battery cell). In some designs, such a polymer layer may be deposited on the membrane or on the electrode, or may simply be sandwiched between the ceramic membrane and at least one electrode. In some designs, such a polymer layer can serve a variety of useful functions. In one example, it can reduce stress concentrations at the interface between the electrode and the porous oxide separator (e.g., because polymers are generally softer and easier to deform compared to oxides). This can result in improved reliability during cell assembly and more reliable cell operation when the cell stack is pressurized. In another example, such a polymer layer can make the oxide separator easier to handle (e.g., during cell assembly or during oxide membrane fabrication). In yet another example, such a polymer layer can enhance adhesion between the oxide membrane and the electrode (e.g., essentially functioning as an adhesive / glue layer). In yet another example, such a polymer layer can improve the electrochemical stability of the oxide film. As previously mentioned, for example, in the case of Li or Li-ion batteries, the use of a polymer layer between the oxide film and the anode can reduce or prevent the reduction of the oxide by Li or other unfavorable interactions at low potentials (e.g., less than about 0.1-2 V vs. Li / Li+, depending on the oxide and electrolyte chemistry). In this case, oxides of aluminum, magnesium, and zirconium can be utilized, as well as many other oxides that are generally unstable or significantly less stable in contact with Li (e.g., silicon oxide, zinc oxide, iron oxide, magnesium oxide, cadmium oxide, copper oxide, chromium oxide, titanium oxide, various combinations of oxides, etc.).When a polymer layer is placed between the oxide film and the cathode, it can prevent or minimize various undesirable interactions between the oxide and the electrolyte or cathode at higher potentials (e.g., above about 3-4 V vs. Li / Li+, depending on the oxide and electrolyte chemistry). In yet another example, such a polymer layer can serve as an additional safety mechanism. For example, it can prevent ion transport (e.g., by closing pores, or by becoming impermeable to electrolyte solvents, or by other mechanisms) when heated above a critical temperature (or cooled below a critical temperature). In some designs, suitable porosity of such a polymer layer can range from about 0 to about 99% by volume (more preferably, from about 10 to about 90% by volume). In some designs, suitable thickness of such a polymer layer can range from about 5 nm to about 20 microns (more preferably, from about 10 nm to about 10 microns). In some designs, a thickness less than about 5 nm may reduce the usefulness of such a polymer layer, while a thickness greater than about 20 microns may unnecessarily increase the overall thickness of the separator stack and induce deleterious effects (e.g., shrinkage of the polymer during heating may also damage the oxide film). In some designs, the polymer layer may be part of a multilayer (including oxide fibers or oxide flakes) membrane, or may be deposited on at least one electrode, or may be prepared as a stand-alone film. The composition of the polymer layer may depend on the particular functionality desired and the particular chemistry of the electrochemical cell, and may be selected from the list of polymer compositions discussed in conjunction with the polymer composites described herein.
[0146] In some applications, it may also be highly advantageous to use small fibers or flakes of oxides (e.g., aluminum oxide, magnesium oxide, zirconium oxide, etc.) or other suitable ceramics (including, but not limited to, porous small fibers and porous small flakes) as thermally stable, electrically insulating, mechanical reinforcement for electrodes, solid (e.g., polymeric, ceramic, glass-ceramic, or composite) electrolytes, and separators of various batteries (e.g., Li and Li-ion batteries, Na and Na-ion batteries, etc.) and other electrochemical energy storage devices. In some designs, the small fibers can improve the mechanical strength, fatigue resistance, and overall durability of the electrodes without introducing undesirable electrochemically active surface area for electrolyte decomposition, e.g., due to the lack of electrical conductivity in aluminum oxide and other oxides as opposed to carbon nanotubes or carbon fibers and nanofibers. Moreover, the use of small fibers of oxides (e.g., aluminum oxide, magnesium oxide, etc.) or other suitable ceramics may be advantageous to provide (and maintain during cycling) fast ion pathways within the electrodes. For example, the pores of small fibers in porous oxides (such as aluminum oxide or magnesium oxide) can be exploited as pathways for ionic access from the top surface of the electrode to the bulk. Some designs can take advantage of such pores to maintain high ionic conductivity in the electrode during cycling because these pores can remain filled with electrolyte and free of electrolyte decomposition products, and because the mechanical strength of the oxide may be large enough to withstand the volume changes of the electrode during operation without inducing pore collapse.
[0147] 6 shows an example of a small oxide fiber coating 601 that includes small lithium aluminum oxide fibers made from small aluminum ethoxide fibers containing lithium impurities. Such small aluminum ethoxide fibers were, in turn, produced by exposing Li-Al alloy particles to absolute ethanol.
[0148] FIG. 7A shows a small oxide fiber (in this example, Al 2 O 3 FIG. 7A shows an example of a composite membrane 701 fabricated by casting from a colloidal solution containing both oxide fibers (PVA, average molecular weight (MW) of about 30,000) and polymer (PVA). The PVA was dissolved in an ethanol solvent, and the oxide fibers were suspended in such solution. A weight ratio of about 91:9 (oxide:polymer) was used in this example. The image shown in FIG. 7A was recorded using a scanning electron microscope (SEM). FIG. 7B shows an example of the bending radius of the composite membrane 701 of FIG. 7A, where a bending radius as small as about 2.5 mm is achieved without breaking. The MW of the polymer can vary over a wide range, but the optimal MW depends on the composition of the polymer, the solvent used, the solubility of the polymer in the solvent, the ratio of polymers, and / or other parameters. In some designs, a suitable MW may range from about 500 to about 5,000,000.
[0149] 8A-8J show several schematic examples of various composite membranes containing small ceramic particles and fabricated according to different exemplary embodiments. FIG. 8A shows the simplest case of a 100% ceramic separator membrane containing small fibers 802A with intervening pores 804A; FIG. 8B shows a ceramic membrane containing the small fibers and pores shown in FIG. 8A, but at the same time further containing a porous polymeric coating 806B on one side; FIG. 8C shows a ceramic membrane containing small fibers, pores and a polymeric coating 806B, but at the same time further containing another polymeric coating 808C on the other side of the ceramic membrane; FIG. 8D shows a ceramic membrane containing small fibers, pores and a polymeric coating 806B, but at the same time further containing another polymeric coating 808C on the other side of the ceramic membrane; FIG. 8E shows a ceramic membrane containing small fibers, pores and a polymeric coating 806B, but at the same time further containing another polymeric coating 808C on the other side of the ceramic membrane; FIG. 8F shows a ceramic membrane containing small fibers, pores and a polymeric coating 806B, but at the same time further containing another polymeric coating 808C on the other side of the ceramic membrane; FIG. 8G shows a ceramic membrane containing small fibers, pores and a polymeric coating 806B, but at the same time further containing another polymeric coating 808C on the other side of the ceramic membrane; FIG. 8B shows a ceramic-polymer composite membrane having a polymer 810D present in the bulk of the membrane (e.g., as a binder) between fibers 812D; FIG. 8E shows a ceramic-polymer composite membrane including small ceramic fibers (or flakes) 818E and polymer fibers (or flakes) 818E; FIG. 8F shows a ceramic membrane including fibers of substantially different diameters and lengths (e.g., long, thick fibers 820F and short, thin fibers 822F); FIG. 8G shows a ceramic membrane including fibrous particles 824G and non-fibrous particles 824G with intervening pores 828G. FIG. 8H shows a ceramic-ceramic composite membrane that includes two or more types (830H and 832H) of fibers of different morphology and / or composition or microstructure; FIG. 8I shows a ceramic composite membrane that includes small fibers 834I that include a coating shell 836I (e.g., made of a polymer or another ceramic layer) on their surfaces; FIG. 8J shows a ceramic composite membrane that includes small ceramic (e.g., oxide 8.) shows a ceramic-polymer composite separator layer including fibers 838J, low aspect ratio ceramic (e.g., oxide) particles 840J filling the gaps between electrode particles 842J (which are in turn electrically connected to electrode current collector 844J), low aspect ratio ceramic (e.g., oxide) particles 846J disposed between the fibers 838J, and a polymer binder 848J, where the ceramic-polymer composite separator layer is coated directly onto an electrode surface (e.g., on a Si-containing anode or other suitable anode or cathode).
[0150] 9 shows an example of a ceramic platelet 901 that may be used in a separator layer coating according to some embodiments of the present disclosure. The ceramic platelet 901 shown in FIG. 9 is a ceramic-containing component of a ceramic-containing separator layer (e.g., Al in this example). 2 O 3 9 represents an example of a flake-shaped configuration of small metal oxide flakes (or platelets) formed from. In one example, flake-type (or platelet-type) small ceramic particles as shown in FIG. 9 can be synthesized by various techniques, including, but not limited to, exfoliation (or partial etching) of layered materials, various deposition techniques (e.g., by chemical vapor deposition, etc.), various solution synthesis techniques (e.g., sol-gel, hydrothermal, solvothermal, heating of reaction solutions containing metal salts, metal alkoxides, metal silicates, or other suitable metal containing precursors, etc.). In a further example, catalysts or capping agents or surfactants may be used in the synthesis of flake-type (or platelet-type) small ceramics (e.g., such as those shown in FIG. 9) in some designs.
[0151] In addition to the use of the above separation membranes comprising small ceramic (e.g. oxides, e.g. aluminum oxide, lithium aluminum oxide, magnesium aluminum oxide, lithium magnesium aluminum oxide, magnesium oxide, lithium magnesium oxide, etc.) fibers in energy storage applications (e.g. in Li-ion and other batteries or supercapacitors), their use in air purification applications (e.g. HEPA filtration) is also very attractive and can be highly advantageous. For example, the high porosity of such membranes (e.g., about 40-80% by volume) can reduce the resistance to air flow and therefore allow for a higher amount of air to be treated (purified) per unit membrane area. In a further example, the small size of the pores in the small fibers can allow for effective rejection (filtration) of submicron particles. In some designs, the high polarity of the oxide fibers (the presence of a high dipole moment on their surfaces) allows such materials to further adsorb smaller particles (than the membrane pore size) due to the strong electrostatic interactions between the surface of the small fibers and the small particles, which allows for more effective filtration (compared to polymeric HEPA filter membranes). In some designs, the high mechanical strength and wear resistance of the ceramic fibers increases the life of the ceramic membrane. Furthermore, in some designs, many of the filtered particles may burn in the air (or plasma) at temperatures lower than the temperature of stability of the all-ceramic membrane. Thus, ceramic membranes based on small fibers may be easily cleaned without much damage. In contrast, certain fiberglass or polymer fiber-based HEPA filters have poor thermal stability and cannot be purified by such means. The good thermal stability of ceramic filters compared to polymer filters may also allow for the effective use of ceramic small fiber-based membrane filters and their long-term stability in hot climates or in applications where temperatures are relatively high (e.g., vehicle filters, various factories, etc.). In contrast, small polymer HEPA filters often degrade rapidly when exposed to high temperatures for long periods of time. Similarly, many polymer membranes lose strength and ductility when exposed to low temperatures. Thus, they may degrade in cold climates.In contrast, ceramic small fiber-based membrane filters do not significantly degrade in their mechanical properties even when cooled below about minus (-) 70°C.
[0152] In some designs, the use of small ceramic (e.g., oxide) fibers (especially porous fibers) is also highly advantageous because their pores (or outer surface) can be easily filled with durable metal or metal oxide-based catalysts (e.g., titanium oxide, copper, copper oxide, iron oxide, copper iron oxide, copper oxychloride, iron oxychloride, copper iron oxychloride, etc.) in the form of nanoparticles or coatings, for example. Such catalysts can serve not only to degrade organic contaminants, but also to effectively kill bacteria, bacterial spores, and viruses. The deposition of such nanoparticles can be done via infiltration based on solutions of precursor salts and their subsequent oxidation (to form oxide nanoparticles) or reduction (to form metal nanoparticles). The large surface area of small fibers (especially small porous fibers) can allow the use of high loadings of one or more catalysts without significant degradation of the membrane's mechanical properties.
[0153] Similarly, it may be advantageous to use the above separation membranes comprising small ceramic (e.g., oxides, e.g., aluminum oxide, lithium aluminum oxide, magnesium aluminum oxide, lithium magnesium oxide, etc.) fibers (including those porous and those formulated with catalysts and antimicrobial agents) for water purification applications, especially when the average pore size achieved is fairly small (e.g., about 0.02 to 0.6 microns). In some designs, such membranes can be very durable and very effective in removing bacteria and various toxic particles from water (e.g., to form drinking water or water safe enough for washing hands, face or body or food (e.g., fruits, berries, vegetables, etc.) or dishes). In some designs, such membranes can be incorporated into straws to allow drinking directly from reservoirs (e.g., lakes, rivers, etc.) that may be contaminated with various harmful bacteria or viruses. Similarly, such membranes can be incorporated into various water containers (e.g., to generate drinking water, etc.).
[0154] This description is provided to enable one skilled in the art to make or use embodiments of the present invention. However, it will be understood that the disclosure is not limited to the specific formulations, process steps, and materials disclosed herein, as various modifications to these embodiments will be readily apparent to those skilled in the art. That is, the general principles defined herein may be applied to other embodiments without departing from the spirit or scope of the disclosure. For example, the described flexible ceramic membrane synthesis may be used in various composite or separator membrane applications in addition to the described uses in energy storage and conversion devices.
Claims
1. 1. A method of manufacturing a battery cell assembly including a first electrode, a second electrode, and a separator, comprising: (A1) providing a dispersion containing metal oxide, metal hydroxide or metal oxyhydroxide fibers and a solvent composition; (A2) coating the dispersion directly onto a roll of the first electrode to form a first layer of the separator on the first electrode; (A3) providing the second electrode; (A4) assembling the first electrode and the second electrode by interposing the separator between the first electrode and the second electrode; The thickness of the separator is in the range of 0.5 μm to 10 μm, the metal oxide, metal hydroxide, or metal oxyhydroxide fibers are characterized by a diameter in the range of 3 nm to 2 μm in diameter and an aspect ratio in the range of 20 to 100,000; The metal oxide, metal hydroxide, or metal oxyhydroxide fibers include (1) a first set of metal oxide, metal hydroxide, or metal oxyhydroxide fibers having a first average diameter and a first average aspect ratio within a first diameter subrange of the diameter range, and (2) a second set of metal oxide, metal hydroxide, or metal oxyhydroxide fibers having a second average diameter and a second average aspect ratio within a second diameter subrange of the diameter range.
2. The method of claim 1 further comprising the step of heat treating at least the first layer at a temperature range of 40°C to 200°C.
3. 2. The method of claim 1, wherein (A3) comprises coating the dispersion directly onto a roll of the second electrode to form the second layer of the separator.
4. The method of claim 1 , wherein the separator does not include a stand-alone separator layer.
5. 2. The method of claim 1, wherein the metal oxide, metal hydroxide, or metal oxyhydroxide fibers contain between 2 atomic % and 40 atomic % aluminum (Al).
6. The method of claim 1 , wherein the separator further comprises a polymer in the range of 0.1% to 50% by weight.
7. The method of claim 6, wherein the polymer comprises a thermoplastic that melts in the range of 70°C to 120°C.
8. The method of claim 6 , wherein the polymer comprises a polymeric binder.
9. The method of claim 1 , wherein at least a portion of the metal oxide, metal hydroxide, or metal oxyhydroxide fibers are bonded to one another by sintering or chemical bonding.
10. The method of claim 1, wherein the porosity of the separator is in the range of 25% to 80% by volume.
11. The total pore volume between the fibers of said metal oxide, said metal hydroxide, or said metal oxyhydroxide is less than 0.1 cm 3 / g to 1 cm 3 The method of claim 1, wherein the molecular weight is in the range of 1 / g.
12. the first electrode is an anode electrode, 2. The method of claim 1, wherein the anode electrode comprises 3% to 70% by weight of silicon (Si).
13. 2. The method of claim 1, wherein the solvent composition comprises one or more of water, alcohol, glycol, glycol ether, ether, N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), methyl ethyl ketone (MEK), hexamethylphosphoramide, cyclopentanone, acetonitrile, tetramethylene sulfoxide, and ε-caprolactone.
14. 10. The method of claim 1, wherein the coating of the dispersion is carried out by spray coating, slot die coating, gravure coating, dip coating, roller coating, and / or knife edge coating.
15. The method of claim 1, wherein the separator exhibits a minimum bend radius in the range of 0.1 mm to 3 cm.
16. The method of claim 1, wherein the separator exhibits a tensile strength in the range of 1 MPa to 1,000 MPa.
17. The method of claim 1, wherein the separator exhibits a pore exclusion size in the range of 10 nm to 1 μm.
18. 2. The method of claim 1, wherein a functional surface coating is deposited on the metal oxide, metal hydroxide, or metal oxyhydroxide fibers to a surface layer thickness in the range of 0.3 nm to 30 nm, the functional surface coating comprising polymer, carbon, dielectric, and / or different ceramic materials.
19. The method of claim 1 further comprising producing fibers of the metal oxide, metal hydroxide, or metal oxyhydroxide by conversion of an alkoxide precursor fiber.
20. the first diameter subrange is from 5 nm to 8 nm; The method of claim 1 , wherein the second diameter subrange is from 40 nm to 60 nm.
21. the first average aspect ratio is 1,000; The method of claim 1, wherein the second average aspect ratio is between 150 and 250.
22. A first electrode, A second electrode, and A separator interposed between the first electrode and the second electrode. Equipped with the separator comprises a first layer comprising metal oxide, metal hydroxide or metal oxyhydroxide fibers, the first layer being deposited directly on the first electrode; The thickness of the separator is in the range of 0.5 μm to 10 μm; the metal oxide, metal hydroxide, or metal oxyhydroxide fibers are characterized by a diameter in the range of 3 nm to 2 μm in diameter and an aspect ratio in the range of 20 to 100,000; The metal oxide, metal hydroxide, or metal oxyhydroxide fibers include (1) a first set of metal oxide, metal hydroxide, or metal oxyhydroxide fibers having a first average diameter and a first average aspect ratio within a first diameter subrange of the diameter range, and (2) a second set of metal oxide, metal hydroxide, or metal oxyhydroxide fibers having a second average diameter and a second average aspect ratio within a second diameter subrange of the diameter range.
23. 23. The battery cell assembly of claim 22, wherein the separator comprises a second layer comprising metal oxide, metal hydroxide, or metal oxyhydroxide fibers, the second layer being deposited on the first layer.
24. 23. The battery cell assembly of claim 22, wherein the separator does not include a stand-alone separator layer.
25. 23. The battery cell assembly of claim 22, wherein the metal oxide, metal hydroxide, or metal oxyhydroxide fibers contain between 2 atomic % and 40 atomic % aluminum (Al).
26. 23. The battery cell assembly of claim 22, wherein the separator further comprises a polymer in the range of 0.1% to 50% by weight.
27. 27. The battery cell assembly of claim 26, wherein the polymer comprises a thermoplastic material having a melting point in the range of 70°C to 120°C.
28. 27. The battery cell assembly of claim 26, wherein the polymer comprises a polymeric binder.
29. 23. The battery cell assembly of claim 22, wherein at least a portion of the metal oxide, metal hydroxide, or metal oxyhydroxide fibers are bonded to one another by sintering or chemical bonding.
30. 23. The battery cell assembly of claim 22, wherein the separator has a porosity in the range of 25% to 80% by volume.
31. The total pore volume between the metal oxide fibers is 0.1 cm 3 / g to 1 cm 3 23. The battery cell assembly of claim 22, wherein the molecular weight is in the range of 1 / g.
32. the first electrode is an anode electrode, 23. The battery cell assembly of claim 22, wherein the anode electrode comprises between 3% and 70% silicon (Si) by weight.
33. 23. The battery cell assembly of claim 22, wherein said separator exhibits a minimum bend radius in the range of 0.1 mm to 3 cm.
34. 23. The battery cell assembly of claim 22, wherein said separator exhibits a tensile strength in the range of 1 MPa to 1,000 MPa.
35. 23. The battery cell assembly of claim 22, wherein said separator exhibits a pore exclusion size in the range of 10 nm to 1 μm.
36. 23. The battery cell assembly of claim 22, wherein the metal oxide, metal hydroxide, or metal oxyhydroxide fibers are provided with a functional surface coating exhibiting a surface layer thickness in the range of 0.3 nm to 30 nm, the functional surface coating comprising a polymer, carbon, dielectric, and / or ceramic material.
37. the first diameter subrange is from 5 nm to 8 nm; 23. The battery cell assembly of claim 22, wherein the second diameter subrange is between 40 nm and 60 nm.
38. the first average aspect ratio is 1,000; 23. The battery cell assembly of claim 22, wherein said second average aspect ratio is between 150 and 250.
39. The battery cell assembly of claim 22; and electrolyte, wherein the electrolyte permeates the separator of the battery cell assembly.
Citation Information
Patent Citations
Separator and its manufacturing method, and nonaqueous electrolyte battery
JP2006164761A
Alumina porous self-supported film and method for manufacturing the same
JP2010105846A
Alumina sol and method for producing the same
JP2010132519A
A method for manufacturing an electrode having a porous coating layer, an electrode formed by the method, and an electrochemical element comprising the same.
JP2012531010A
Separator
JP2013125731A